RLX-2 ameliorates post-traumatic joint contracture by inhibiting the cGAS-STING signaling pathway - Jian-Jun Chen; Quan-Bing Zhang; Yan Wang; Chen Chen; Yi Liu; Zun-Yu Du; Xiu-Li Kan; Han Xiao; Xue-Ming Li; Run Zhang; De-Ting Zhu; Xian-Liang Rao; et al. (Tissue and Cell, 2027)

Lactate-enhanced production of a cyclic β-1,2-glucan in Acetobacter pasteurianus - Yong Chen; Yihang Qi; Zhongya Zhou; Xin Liu; Yaping Sun; Ting Liu; Mengru Wu; Hui Li; Jing-yi Zhao; Zijun Xiao (Food Microbiology, 2027)

Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

Phosphorus-driven electronic modulation on CoP/Co@NC heterostructures for highly efficient and stable hydrogen production in NaBH4 hydrolysis - Kai Jia; Yuhui Qian; Suning Li; Fuying Wu; Guoqiang Liu; Beibei Xiao; Ting Bian; Petr Senin; Liuting Zhang (Fuel, 2026)

Astragaloside IV pretreatment enhances the therapeutic efficacy of bone marrow mesenchymal stem cells in murine fulminant hepatic failure - Ting-Ting Zhao; Wen-Qiang He; Rui-Zhi Shi; Bing-Yu Du; Mei-Mei Lan; Dan Zhou; Xiao-Qin Gao; Min Li; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Oleanolic acid modulates neuronal regeneration through KLF5-mediated FGF13 mRNA degradation to alleviate Alzheimer’s disease-like cognitive dysfunction - Dan Ren; Jiangxi Xu; Lan Xiao; Ting Zhang; Biyan Li; Ruomeng Li; Hong Zhu (Journal of Molecular Medicine, 2026)

Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

XsiAMT1.1a was identified as a novel ammonium uptake functional gene and its overexpression combined with GA4 application significantly increased yield in Arabidopsis thaliana - Xiao Han; Zhao-Hua Gong; Jie Cao; Li-Na Ye; Yuan Cheng; Yu-Xuan Du; Ting-Ting Zhao; Hai-Long Wu; Chang Zhang (Plant Science, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

Saebias A–G, eudesmane sesquiterpenes from Salvia plebeia with potential for Alzheimer's disease prevention via anti-neuroinflammatory and neuroprotective effects - Xiao-Die Shu; Han-Fei Liu; Yu-Qiong Liao; Wan-Jun Pu; Ting Zhao; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

COX-2 inhibitors from Laportea bulbifera: Structure-activity relationship, kinetic investigation, and molecular docking - Linlan Tao; Yanan Li; Zipeng Gong; Feng Zhang; Jue Yang; Lei Huang; Ting Xiao; Ping Yi; Xiaojiang Hao; Chunmao Yuan (Phytochemistry, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Dandelion-like Pd/Cu nanozyme with multi-enzyme activities: A colorimetric sensor array for PFAS discrimination - Hui-ting Hu; Xiao-mei Li; Wen-cai Jiang; Chen Ni; Yu-yang He; Guo-qi Zhang; Hao Yu; Zhi-Bo Hou (Analytica Chimica Acta, 2026)

Bubble-enhanced micromixing in an enzyme/MnO2 system immobilized in a covalent organic framework for boosting enzymatic catalysis - Zheng-Feng Zhang; Jia-Yi Shao; Hui-Ting Li; Xiao-Hui Yao; Wei-Guo Zhao; Xin Chen; Dong-Yang Zhang (Sustainable Chemistry and Pharmacy, 2026)

Kinetics and characterization of jarosite biosynthesis via Acidithiobacillus ferrooxidans: Elucidating its potential in acidic uranium tailings stabilization - Ling Xiao; Shangze Li; Jing Sun; Qian Li; Guangyue Li; Zhao Cui; Ting Li; Xiaowei Zhou; Qinghua Li (Minerals Engineering, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Integrating ecological networks and metagenomics to decipher core microbial drivers of organic acid metabolism during heaped fermentation of sauce-flavor Baijiu - Hong-Yan Zhang; Ting-Cai Huang; Li-Juan Chai; Wei Shi; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Research International, 2026)

Decoding the thermocyclic solar-driven fermentation: Multi-omics insights into microbial and metabolic dynamics of traditional Chishui river basin soy sauce - Wei-Qin Deng; Zhen-Ming Lu; Xiong-Bo Li; Zhi-Yi Fan; Ting Li; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Chemistry, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

HYDRA-EDGE: HYDrogel-based rapid assay with entropy-driven gel enhancement for point-of-care viral detection - Ailing Yang; Li Zhou; Jing Li; Yu Liu; Ting Xiao; Qingxiang Yang; Dunquan Xu; Jiezhong Deng; Ming Chen; Sha Yang (Chemical Engineering Journal, 2026)

Differential host choices of Helicoverpa armigera and H. assulta to tomato - Jie-Wen Mao; Qian-Wen Luo; Shao-Ting Duan; Meng-Hao Zhang; Xiao-Guang Liu; Xian-Ru Guo; Yan-Min Liu; Wei-Zheng Li (Arthropod-Plant Interactions, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Thermally synergized electron shuttling via Cu-O-Fe bridge redirects H2O2 activation pathways - Wei-bang Xie; Dan Zheng; Kai-kai Chen; Jing Liu; Wen-jie Ju; Zhong-ting Hu; Mian Hu; Chun-shan Lu; Zhi-yan Pan; Xiao-nian Li (Water Research, 2026)

Thermal mechanisms driving Neoarchean ultrahigh-temperature metamorphism in a sagduction regime: numerical constraints from the North China Craton - Ying Li; Ting Yang; Chenying Yu; Qihang Wu; Changqing Yin; Jiahui Qian; Xiao Wang; Chuan Huang; Jian Zhang (Precambrian Research, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Early Cretaceous Jehol Biota in the Qinling Orogenic Belt: palaeobiogeographical and palaeoecological implications - Siyu Song; Xin Zhang; Xiao Teng; Ting Li; Tingting Yu; Jiahao Li; Yan Xue; Peihan Liu; Rui Fang; Xiangdong Zhao; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Polystyrene microplastics induce auditory neurotoxicity in mammals: Integrated multi-omics profiling reveals oxidative damage and synaptic molecular dysregulation - Huanzhi Wan; Jingchun Liu; Xuan Yu; Ting Li; Wenting Yu; Bo Liu; Yingzhao Liu; Yuanyuan Zhang; Shimin Zong; Qingquan Hua; Hongjun Xiao (Journal of Hazardous Materials, 2026)

Computer simulation analysis of the sensitivity of freezing temperature, product properties and a multi-stage strategy on liquid nitrogen spray freezing characteristics of large yellow croaker - Yuxiao Mao; Yiqing Zhang; Hosahalli S. Ramaswamy; Hongyue Li; Mingyun Dai; Tao Song; Ting Xiao; Yong Yu; Songming Zhu (Journal of Food Engineering, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

Glucose glycosylation enhances the functional properties of grass carp scale gelatin-derived TIPs via gut microbiota and metabolite regulation - Zi-Zi Hu; Ting-Ting Wu; Xin Li; Chun-Yan Peng; Su-Su Ye; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2026)

UEV1A attenuates MDA5-mediated antiviral immune response by reducing its ubiquitination and aggregation - Jiaxin Wang; Rongyao Sun; Ting Li; Houcheng Liang; Huan He; Jun Xiao; Hui Wu; Yong'an Zhang; Hao Feng (Fish & Shellfish Immunology, 2026)

Nano-confined MXene/covalent organic framework photothermal bioreactors for efficient catalysis and temperature control - Chen-Xi He; Hui-Ting Li; Jia-Ying Chen; Zhen-Feng Zhang; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Bioresource Technology, 2026)

Benzoic acid inhibits peach root growth and lateral root emergence by disrupting auxin homeostasis through salicylic acid accumulation - Qing Rong Zhang; Jilin Yao; Feiyang Ji; Zhilin Sun; Bing Bai; Jun Zhao; Huchen Li; Yueping Liu; Qingqin Cao; Qing Zhang; Ting Ting Xiao (Plant Cell Reports, 2026)

Correction: Beyond rice: persistent wetland plant use in the northwestern Tai Lake region during the 7th millennium bp - Jie Tian; Moran Li; Xiao Long; Ting An (Vegetation History and Archaeobotany, 2026)

Beyond rice: persistent wetland plant use in the northwestern Tai Lake region during the 7th millennium bp - Jie Tian; Moran Li; Xiao Long; Ting An (Vegetation History and Archaeobotany, 2026)

Comprehensive Transcriptomics and Biochemical Analysis Provide New Insights into the Light Intensity Regulation Growth and Medicinal Quality of Dendrobium nobile - Ting Li; Haolin Liu; Yijun Fan; Hui Wang; Linlong Xu; Siyu He; Jie Ma; Junlan Wu; Chunhong Mou; Meng Zhao; Li Chen; Xuyang Liu; et al. (Journal of Plant Growth Regulation, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Time-dependent citrate-mediated precipitation inhibition in uranium column leaching: Mechanistic insights into pore evolution and uranium migration - Xiaowei Zhou; Jing Sun; Qian Li; Guangyue Li; Shangze Li; Ling Xiao; Hong Shu; Haiying Fu; Ting Li; Yongdong Wang; Zhao Cui; Guosen Xie (Journal of Hazardous Materials, 2026)

Atmospheric bulk deposition of microplastics in Jiuzhaigou World Natural Heritage Site: Tourism-associated divergence between particle number and polymer mass fluxes - Ting Liu; Yunqian Chen; Weiyang Xiao; Lv Zhou; Yutao Cao; Philip K. Hopke; Dongmei Liu; Jiangbin Shu; Hui Liu; Rongqiu Li; Xue Qiao (Journal of Hazardous Materials, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

Interfacial electronic reconstruction and near-zero hydrogen adsorption energy in Ru-modulated Ni2P/CoP nanowire arrays for on-demand chemical hydrogen evolution - Zichuan Lu; Fuying Wu; Kai Jia; Suning Li; Beibei Xiao; Ting Bian; Petr Senin; Liuting Zhang (Chemical Engineering Journal, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Decoding immunotherapy resistance in multiple myeloma: genetic insights and approaches to counter resistance - Huan Li; Qi Xia; Mei Yu; Ying Lv; Jialing Xiao; Xiaoxin Guo; Kai Dong; Yu Zhou; Ling Zhong; Ting Wang; Weijia Wu; Chengzi Gan; et al. (Science China Life Sciences, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Effects of photoperiod on gonadal development and neuropeptide Y and NPY1 receptor in Nile tilapia (Oreochromis niloticus) - Yujie Cao; Jun Xiao; Pengfei Gao; Yufang Chen; Zhanyang Tang; Liping Li; Zhongbao Guo; Ming Li; Zhuanling Lu; Ting Huang (Fish Physiology and Biochemistry, 2026)

Plant growth stage drives the differentiation of microbial assemblage across plant niches - Li Shao; Jiajun Li; Ting Lu; Tangfu Xiao; Aiwen Wu; Xiuping Li; Jinmei Deng; Enzong Xiao (Applied Soil Ecology, 2026)

Tumorigenesis of well-differentiated and dedifferentiated liposarcoma: 12q amplicon architecture, oncogenic cargo, and evolutionary progression - Aobo Zhuang; Xiao Zhou; Chengfei Xu; YangJu Chen; Xueling Wang; Runchun Li; Jiajing Hu; Yinxue Cheng; Yunyan Wan; Ting Wu; Wengang Li (Cancer and Metastasis Reviews, 2026)

Impact and evaluation of different temporal compositing strategies on the accuracy of tea plantation remote sensing mapping - Deng Zhi-Yong; Wu Guo-Hui; Liu Xiao-Jing; Yang Ya-Jie; Luo Jian; Zhang Hai-Yao; Du Xin-Lu; Li Ting; Wang Shan (International Journal of Remote Sensing, 2026)

Chemical constituents from the roots of Illigera celebica - Si-Feng Yang; Lin-Wen Yi; Qiu-Xia Huang; Xing-Meng Luo; Xiao-Bing Su; Lin Hu; Wen-Ting Li; Xiang-Zhong Huang; Meng-Yuan Jiang (Natural Product Research, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

A new species and a newly recorded species of the genus Hua (Gastropoda: Semisulcospiridae) from the Chishui River, Yunnan, China - Jian-Fu Wei; Yuan-Chao Chen; Xue-Hua Li; Guang-Can Zhou; Qi-Yan Zhu; Ting-Song Yu; Jun-Xing Yang; Xiao-Ai Wang (Molluscan Research, 2026)

Single-cell profiling reveals clonal CD8+T cell-derived IFNγ drives Sjögren’s disease-related dacryoadenitis - Hao-Xian Zhu; Fang-Fang Li; Xiao-Min Chen; Bing-Yang Zhang; Ting Xu; Zhe-Xiong Lian; Cai-Yue Gao; Qian-Li Meng (Inflammation Research, 2026)

Unravelling flavor formation in Chinese steamed bread made with fermented glutinous rice wine dough: insights from microbial succession, metabolomics, and volatile profiling - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Research International, 2026)

Correction: Mitophagy protects renal tubular epithelial cells from intermittent hypoxia-induced injury via the HIF-1α/BNIP3 pathway - Xiao-Bin Zhang; Qi-Feng Gan; Yu-Xin Guo; Li-Da Chen; Li-Qin Zhang; Ling Cai; Ya-Ting Yuan; Jing-Huang Cai; Xiang-Xin Chen (Sleep and Biological Rhythms, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

Phage-Display Identification of Urate-Binding Cyclic Peptides with Preliminary Urate-Lowering Activity in Adenine-Induced Hyperuricemic Rats - Mi Ai; Zhi-Ming Wang; Wei-Lin Guo; Xue-Qi Li; Li-Ting Xiao; Yan-Shan Mai; Hong-Bin Zhang (International Journal of Peptide Research and Therapeutics, 2026)

Bushen Huoxue Acupuncture alleviates alzheimer’s disease progression via the E3 ubiquitin ligase SMURF2‑mediated ubiquitination of LAPTM5 - Ruomeng Li; Ting Zhang; Dan Ren; Hong Zhu; Jiangxi Xu; Lan Xiao (Metabolic Brain Disease, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Four new cysteine derivatives with cytotoxic activity from Poecilobdella manillensis - Qingqing Fan; Peixing He; Hang Xiao; Juan He; Ting Wang; Zhenbei Lan; Feng Tian; Jianyuan Tang; Li Ma (Phytochemistry Letters, 2026)

Disrupting the lepidolite structure via low-temperature (NH4)2SO4 and Na2SO4 roasting: Achieving efficient co-extraction of lithium, rubidium, and cesium from lepidolite - Shuping Cheng; Zhipeng Rao; Jiezhong Zou; Junfeng Zhang; Guobiao Li; Huiquan Li; Ting Lai; Wanhai Xiao; Yong Lin; Tinggang Li; Dong Wang (Journal of Environmental Chemical Engineering, 2026)

The conversion of ether into ester functional groups of porous carbon through altering intramolecular condensation pathways - Ting Xiao; Yin Yang; Yulong Li; Chen Zhang; Changbo Lu; Qiankun Xiang; Henglong Ren; Shengping Li; Haipeng Song; Yindong Liu; Luhai Wang; Xinlong Ma (Chemical Engineering Journal, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Study of maximum wave arrival time of landslide-tsunami in narrow reservoirs based on wavelet transform analysis - Jizhixian Liu; Ye Li; Yang Wang; Yani Lu; Zhijiang Li; Ting Xiao (Bulletin of Engineering Geology and the Environment, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

The major chemical constituents of Penthorum chinense Pursh and their inhibitory activity against enzymes associated with metabolic dysfunction-associated steatotic liver disease - Chao-Qun Wang; Meng-Qi Wang; Xiao-Na Gan; Ting-Zhao Li; Xiang-Wei Zheng; Bo Li; Xin Fang; Shuang Liang (Natural Product Research, 2026)

Fast-response Phosphorescence Sensor for Dissolved Oxygen Detection Based on PtOEP/TiO2/CB@PFFE Sensing Film - Jia Xiao; Minmin Han; Ting Li; Baohua Yue; Liuming Yan (Journal of Fluorescence, 2026)

Characterization and source apportionment of halogenated organic pollutants in sediments from the Daya Bay, South China Sea - Ren-Jie Shang; Jian-Fang Hu; Ming-Yang Liu; Yao Xiao; Yi-Ting Zeng; Li-Tian Huang; Ping-An Peng (Marine Pollution Bulletin, 2026)

Biocontrol of tobacco bacterial wilt by Bacillus velezensis Y19: insights into chemotaxis, competition and antagonism - Yajie Hu; Xiaolan Yang; Huiping Wu; Qunling Li; Guangxiong Xiao; Feng Wu; Feng Li; Zihua He; Xiaoxing Lin; Ting Ding (Physiological and Molecular Plant Pathology, 2026)

Efficient remediation of multi-PTE contaminated farmland by synergistic dissolution of soil metal oxides using wood vinegar and FeSO4 co-washing - Tianying LÜ; Xinlei JI; Xiaoxun XU; Guochun LÜ; Changlian XU; Guiyin WANG; Shirong ZHANG; Zhanbiao YANG; Zhang CHENG; Junzhuo CAI; Heng LÜ; Ting LI; et al. (Pedosphere, 2026)

Phylotranscriptomics reveals conflicts of deep nodes in Saxifragales - Hui-Ling Li; Hong Chang; Huan-Huan Xie; Lei Zhang; Guo-Qian Hao; Dimitar Dimitrov; Peng-Chuan Sun; Nathanael Walker-Hale; Jia-Liang Li; Xiao-Ting Xu (Molecular Phylogenetics and Evolution, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Experimental study on microwave-assisted mechanical fragmentation of simulated vesicular mare basalt - Liang-Xiao Chen; Zheng-Wei Li; Xia-Ting Feng; De-Tian Li; Cheng-Dan He; Xian-Qiang Li; Yong-Jun Wang; Wen-Feng Guo; Jian Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Analysis of quality deterioration of buckwheat hele noodles during freezing storage: oxidation of lipids and proteins - Ting Yu; Yalei Li; Ruiming Luo; Shuang Gao; Qijian Jiang; Mengyao Ma; Lingling Zhang; Yuying Xiao (Food Chemistry, 2026)

Elucidating the synergistic SO2 tolerance mechanism in Cu-doped BiFeO3 electrocatalysts for sustainable nitrate reduction - Yuxiang Li; Yaao Li; Qian Yang; Ting An; Xiao Cui; Liuyun Lai; Yaoxin Wu; Chenxia Yang; Dalei Chang; Aiqun Kong; Denghao Wang; Jiajun Wang; et al. (Chemical Engineering Journal, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

An AcMYB10-AcF3GT1/GST1 module restricts anthocyanin synthesis in the fruit flesh of kiwifruit - Xiao-tian Li; Zhi-xia Huang; Yu-xiao Zhai; Ya-ting Guo; Yi-tong Liu; Yan Zhang; Zhu Xie; Andrew C. Allan; Xue-ren Yin; Wen-qiu Wang (Plant Cell Reports, 2026)

Microneedle-mediated delivery of hydroxypropyl-β-cyclodextrin-encapsulated Angelica sinensis (Danggui) essential oil for acne treatment: efficacy and mechanisms - Xiaoli Liu; Xiaojuan Li; Weijun He; Xiaoyu Han; Ting Xiao; Shiqi Guo; Yujie Jia; Liqun Lin; Ming Yang; Li Wang; Yuehong Xu (Drug Delivery and Translational Research, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Probiotic novel strain Lactobacillus reuteri MRD01 alleviates dextran sulfate sodium-induced colitis in male mice by promoting intestinal barrier integrity - Ying Li; Guoao Ding; Guoan Bao; Xiaojun Lai; Ruxin Ye; Ting Wang; Yujie Du; Ke Xiao; Peng Zhou; Jingjing Wang; Xin Xia; Yan Zhang (Antonie van Leeuwenhoek, 2026)

Vascular endothelial growth factor (VEGF)-related blood flow regulation and anti-inflammation in the protection of Danzhu Fuyuan Granules against cognitive impairment - Yu Duan; De-Wei Zhu; Qin Liu; Xing-Yuan Li; Xiao-Ting Zhou; Jing-Qing Hu; Ai-Jun Liu (Metabolic Brain Disease, 2026)

Two new sesquiterpenes from Ainsliaea glabra - Xiao-Li Ma; Guo-Dong Jiang; Ji-Yuan Wei; Ze-Dong Nan; Chang-Ting Zhang; Zhi-Jun Song (Natural Product Research, 2026)

Magnetic biochar- loaded nano zero-valent iron for heavy metal passivation: Coupled interaction mechanism between arsenic and cadmium - Yi Hu; Huanhuan An; Xinquan Wei; Ting Liu; Xiao Tang; Li Hua; Dongmei Hou; Xiao Xiao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

A study on the association between early-pregnancy hair metal levels and gestational diabetes mellitus - Feng Tang; Jun Guo; Li-An-Sheng Wu; Xiao-Yuan Fan; Han-Wen Zhang; Noora Kartiosuo; Boris Novakovic; Ting-Li Han; Hua Zhang; Yin-Yin Xia; Philip Baker; Richard Saffery (Environmental Pollution, 2026)

Thermal runaway behaviour induced by localised aluminium-water reaction at low temperature - Hai-Fang Mao; Jia-Wei Fang; Yi-Kang Deng; Jun Zhang; Yan-Li Zhao; Yao Feng; Min Xiong; Hui-Ting Gu; Xiao Feng; Jian-Hao Fang; Jian-Hua Chen; Chi-Min Shu; et al. (Chemical Engineering Journal, 2026)

Rapid urine protein detection for CKD diagnostics using a high-sensitivity PDA-coated infrared fiber sensor - Shun Li; Ting Fang; Yongkun Zhao; Yinsheng Xu; Yami Ling; Ming Wang; Xiangpan Li; Jiang Zou; Wei Xiao; Guangchao Zang; Xianghua Zhang (Chemical Engineering Journal, 2026)

Co-solvent-modulated polyamide nanofiltration membranes for high-temperature separation - Wan-Long Li; Xiao-Wei Luo; Wan-Ting Lin; Si-Yuan Zhang; Zi-Lu Zhang; Zi-Jun Zhang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2026)

Mitophagy protects renal tubular epithelial cells from intermittent hypoxia-induced injury via the HIF-1α/BNIP3 pathway - Xiao-Bin Zhang; Qi-Feng Gan; Yu-Xin Guo; Li-Da Chen; Li-Qin Zhang; Ling Cai; Ya-Ting Yuan; Jing-Huang Cai; Xiang-Xin Chen (Sleep and Biological Rhythms, 2026)

Protective role and mechanism of sonic hedgehog signaling pathway in spinal cord injury - Li Li Yin; Xiao Zhen Ji; Min Tang; Li Hui Chen; Jiu Zhou Lin; Ya Ling Jin; Wei Ting Chen (Molecular & Cellular Toxicology, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Decumbic acid derivatives from soil fungus Lasiodiplodia sp. BG1083 - Hong-Qiao Dai; Xiao-Bing Su; En-Tao Zhou; Wen-Ting Li; Shuang-Shuang Chen; Hui-Yang Cao; Lin Hu; Meng-Yuan Jiang (Natural Product Research, 2026)

The transcription factor BRN2 confers cadmium tolerance by regulating SAM1 expression in Arabidopsis - Su Li; Jing Huang; Jia Qi Li; Chuan Jin Shan; Ren Fang Shen; Da Li Zeng; Jin Chen; Xian Jiao Guan; Xiao Fang Zhu; Ting Wu Liu; Yong Gang Xu (Plant Science, 2026)

Microwave-assisted extraction enhances the epicatechin and bovine serum albumin the interaction by inducing protein conformational changes - Wen-Ting Duan; Jiang-Feng Yuan; Li-Juan Wang; Meng-Xue Sun; Xiao-Wen Yang; Zhi-Jun Qiu (Food Chemistry, 2026)

Dual waste-derived 3D solar evaporator with vertically aligned channels for efficient solar-driven desalination, wastewater purification, and thermoelectricity generation - Xin Wang; Yicheng Wang; Xiao Sun; Xiaowen Cui; Tinghui Wu; Ting Wang; Yiran Luo; Yongqi Yang; Mengzhu Liu; Yongpeng Wang; Zhe Chen; Jing Li (Desalination, 2026)

Membrane aerated biofilm reactor for largely enhanced nitrogen removal in low carbon/nitrogen ratio municipal wastewater: integrating nitrification, partial denitrification, and anammox - Xiwei Cao; Lin Zhang; Haoran Tu; Ting Li; Guofeng Wang; Ling Xiao; Yupeng Zhang; Peng Liu; Yi Li; Jiaye Li; Xinglin Li; Boyang Hu; et al. (Bioresource Technology, 2026)

ESIRA, a novel framework integrating efficacy and safety for evaluating first-line treatments in advanced hepatocellular carcinoma - Hai-Long Li; Hui Zhou; Yi-Yang Zhang; Jin-Ting Lai; Zhen-Zhong Zhou; Jing-Yi Huang; Song-Bin Guo; Yu Wang; Wei-Juan Huang; Xiao-Peng Tian (Science China Life Sciences, 2026)

Alisol B 23-acetate alleviates high-fat diet-induced insulin resistance by activating the SIRT1/FOXO1 axis and PI3K/AKT pathway - Wenjun He; Zhenxuan Kong; Jingshu Cai; Zhuyun Wang; Li Ma; Xiaoqiu Xiao; Ting Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Taurine Alleviates Sepsis-Induced Myocardial Injury by Inhibiting NF-κB Pathway-Mediated Inflammation, Mitochondrial Dysfunction, and Apoptosis - Junkai Feng; Ting Ma; Liu Yang; Min Li; Dahai Xiao; Pengxin Gong; Ani Zhao; Pu Li; Linong Yao (Cardiovascular Toxicology, 2026)

Preliminary design and analysis of a radar system model based-on a phased-array RF astro-receiver for space debris detection and tracking - Lalida Tantiparimongkol; Ming Shen; Peng-qi Gao; Xiao-zhong Guo; Huan-huan Yu; Jia-wei Li; Jia-lang Ding; Yu-ting Chu; Ran Duan; You Zhao (Advances in Space Research, 2026)

Design, synthesis and activity evaluation of usnic acid monoesterification derivatives - Qing Zhang; Jun-Li He; Xiao-Xia Zhuo; Yi-Meng Hao; Hong-Ting Duan; Yan Jia; Jing-Jing Wang; Li-Ning Wang (Natural Product Research, 2026)

Iridoid glycosides and phenolic glycosides from Gentiana rhodantha and their anti-inflammatory activities - Han-Fei Liu; Wan-Jun Pu; Ting Zhao; Xiao-Die Shu; Jun-Jie Lan; Chao Chen; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Expanded species diversity of fungi in metalliferous mine tailings ponds and their potential ecological roles revealed by PacBio sequencing - Yanying Li; Ting Huang; Weihang Zeng; Rongzhou Jin; Ye Wu; Zhipeng Chen; Qijie Cheng; Xinlin Yu; Xiao-lin Luo; Guan-xiong Wu; Jia-wei Li; Pu Jia; et al. (Journal of Hazardous Materials, 2026)

The role of geography and regional climate in shaping the chemical profiles and biological potentials of Citrus essential oils - Wenbin Xiao; Jiajing Guo; Yanfang Liao; Yanjiao Fu; Zixuan Li; Tongping Zhang; Ting Liu; Yangbo Xiao; Xuebo Shang; Zhipeng Gao; Yang Shan (Food Chemistry, 2026)

Immunological and behavioral biomarkers of Vibrio vulnificus exposure in zebrafish: Implications for aquaculture biosecurity and pathogen surveillance - Duo Chen; Qiangqiang Xiao; Jiapeng Wang; YiLin Huang; Zhenlu Li; Chenhuan Dong; YuanXin Liang; Youqiang Chen; Ting Xue; Chentao Lin (Fish & Shellfish Immunology, 2026)

Structural elucidation, in vivo tracking and pharmacokinetic profiling of a novel polysaccharide with anti-migraine efficacy - Lingxian Liu; Haibo Li; Junran Shao; Ting Li; Zhenzhong Wang; Xinsheng Yao; Wei Xiao; Yang Yu (Carbohydrate Polymers, 2026)

Transcriptomic and physiological insights into Diethylstilbestrol toxicity in Phaeodactylum tricornutum - Dong-Sheng Zhao; Xiao-Li Liu; Yu-Ting Chen; Huan Yang; Muhammad Ahsan Farooq; Xiufeng Yan; Hui-Xi Zou (Aquatic Toxicology, 2026)

Byakangelicol Alleviates Ischemic Brain Injury by Inhibiting Microglial Activation and Oxidative Stress - Xiao Wan Wang; Yan Qiong Fu; Zhuo Li Li; Ting Li; Hui Lan Wang; Yu Zheng; Chan Zhang; Miaolin Zeng; Chan Li; Dewei Xie; Bai Hui Chen (Molecular Neurobiology, 2026)

Brevibacillus nigriterrae sp. nov., a Novel Denitrification Bacterium Isolated from Black Soil - Jun Xiao; Xin-Ting Yuan; Le-Bin Chen; Yu-Ting OuYang; Xin Huang; Jia-Hao Tan; Jun Liu; Shuang Wang; Jian-Yu Jiao; Wen-Jun Li (Current Microbiology, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Straw-induced hematite-to-magnetite conversion in alkaline media: Experimental study and potential in Bayer process - Xin He; Guo-zhi Lv; Bing-shen Liu; Qing-dong Li; Xiao-lei Zhang; Zhuang-zhuang Yun; Ting-an Zhang (Minerals Engineering, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Snowflake ZIF-8/Cu2S: A novel adsorbent material for efficient capture of radioactive iodine - Shu-Xuan Li; Xuan Zhao; Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Ao-Tian Gu; Peng Wang; Chun-Hui Gong; Ji-Gen Lu; Yi Yang (Journal of Environmental Chemical Engineering, 2025)

Interactive effect of various fatty acids and the Maillard reaction of sesame meal enzymatic hydrolysates on aroma generation - Qing-qing Ruan; Bei-bei Hu; Kai-yue Su; Jun-ru Li; Wen-ting Yin; Zi-qi Han; Yu-xin Liu; Xiao-shuang Cai (Food Research International, 2025)

Effect of sample volume on the variation of freezing characteristics, mechanical properties, and microstructure of gelatin gel with depth after liquid nitrogen spray freezing - Yuxiao Mao; Hosahalli S. Ramaswamy; Hongyue Li; Mingyun Dai; Tao Song; Ting Xiao; Junde Ren; Yiqing Zhang; Yong Yu; Songming Zhu (Food Research International, 2025)

Multi-omics network analysis of flavour formation in golden-flowered Tibetan dark tea processed by “flowering” using raw materials with different fermentation degrees - Ting Zhang; Zhiying Xu; Xue Yang; Meiyi Ning; Mengyi Ren; Xiao Liu; Yun Wang; Chunhua Li; Chen Xia; Manyou Yu; Shengxiang Chen; Xiaobo Tang; et al. (Food Chemistry, 2025)

Automatic immunomagnetic beads clean-up coupled with HPLC-FLD for rapid, simple and high-throughput detection of zearalenone in cereal foods and feeds - Zhiming Xiao; Jun Zhang; Yinji Jin; Bo He; Ting Yao; Jing Tian; Fan Mo; Decheng Suo; Shi Wang; Runxian Li; Lijie Zhang; Shen Hu; et al. (Food Chemistry, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

SOX11-mediated CBLN2 Upregulation Contributes to Neuropathic Pain through NF-κB-Driven Neuroinflammation in Dorsal Root Ganglia of Mice - Ling-Jie Ma; Tian Wang; Ting Xie; Lin-Peng Zhu; Zuo-Hao Yao; Meng-Na Li; Bao-Tong Yuan; Xiao-Bo Wu; Yong-Jing Gao; Yi-Bin Qin (Neuroscience Bulletin, 2025)
Neuropathic pain, a debilitating condition caused by dysfunction of the somatosensory nervous system, remains difficult to treat due to limited understanding of its molecular mechanisms. Bioinformatics analysis identified cerebellin 2 (CBLN2) as highly enriched in human and murine proprioceptive and nociceptive neurons. We found that CBLN2 expression is persistently upregulated in dorsal root ganglia (DRG) following spinal nerve ligation (SNL) in mice. In addition, transcription factor SOX11 binds to 12 cis -regulatory elements within the Cbln2 promoter to enhance its transcription. SNL also induced SOX11 upregulation, with SOX11 and CBLN2 co-localized in nociceptive neurons. The siRNA-mediated knockdown of Sox11 or Cbln2 attenuated SNL-induced mechanical allodynia and thermal hyperalgesia. High-throughput sequencing of DRG following intrathecal injection of CBLN2 revealed widespread gene expression changes, including upregulation of numerous NF-κB downstream targets. Consistently, CBLN2 activated NF-κB signaling, and inhibition with pyrrolidine dithiocarbamate reduced CBLN2-induced pain hypersensitivity, proinflammatory cytokines and chemokines production, and neuronal hyperexcitability. Together, these findings identified the SOX11/CBLN2/NF-κB axis as a critical mediator of neuropathic pain and a promising target for therapeutic intervention.

Correction: Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2025)

Proteomics revealed the underlying mechanism of STAT1-induced cognitive deficits in 2-month-old C57 mice - Xiao Li; Ting Li; Bocheng Xiong; Juan Luo; Xifei Yang; Yan Feng (Experimental Brain Research, 2025)

3D reconstruction of the ovariole in Nilaparvata lugens (Hemiptera: Delphacidae) by FIB-SEM - Ke-Qi Ye; Guan Wang; Jian-Sheng Guo; Chuan-Xi Zhang; Xiao-Ping Yu; Dan-Ting Li (Cell and Tissue Research, 2025)

Domain Adaptation with Deep Feature Clustering for Pseudo-Label Denoising in Heterogeneous SAR Image Classification - Sheng-Jie Luo; Zhi-Gang Liu; Xi-Hai Li; Yi-Ting Wang; Xiao-Niu Zeng; Zhi-Hao Zheng; Heng Li (Applied Geophysics, 2025)

Plasma-activated water: A novel approach to modulating main pectin, hemicellulose and cellulose metabolism in goji berry cell walls - Kai-Ping Cong; Ting-Ting Li; Cai-E. Wu; Gong-Jian Fan; Dan-Dan Zhou; Xiao-Jing Li; An-Di Suo (Postharvest Biology and Technology, 2025)

Biogenic jarosite coating as an innovative passivator for acidic uranium residue stabilization using Acidithiobacillus ferrooxidans - Shangze Li; Ling Xiao; Jing Sun; Qian Li; Guangyue Li; Zhao Cui; Ting Li; Xiaowei Zhou (Journal of Hazardous Materials, 2025)

Self-sustained Bio-Fenton system driven by Shewanella oneidensis for efficient degradation of persistent organic pollutants under oxygen-limited conditions - Yang-Yang Fan; Xuan Yao; Zhi-Yong Li; Xin-Yu Yang; Ming-Juan Zou; Zi-Yi Zhang; Kun Wu; Ting Huang; Ya-Ning Sun; Xiang Xiao (Journal of Hazardous Materials, 2025)

Developing and validating a model food using gelatin gel for liquid nitrogen spray freezing of Larimichthys crocea: Thermal properties, freezing characteristics, and microstructure - Yuxiao Mao; Hosahalli S. Ramaswamy; Junde Ren; Hongyue Li; Tao Song; Ting Xiao; Sinan Zhang; Yong Yu; Songming Zhu (Journal of Food Engineering, 2025)

Engineered Plasmonic multi-hot spots on magnetic Nanospheres for quantitative detection of pesticide residues on food surfaces via SERS tagging analysis - Ming-Jie Wan; Yu-Ting Wu; Yan-Hui Wang; Xiao-Hang Wu; En-Ming You; An Wang; Sheng-Hong Liu; Jin-Chao Chen; Yue-Jiao Zhang; Shangzhong Jin; Fan-Li Zhang (Food Chemistry, 2025)

Impact of lactic acid bacteria-mediated semi-solid fermentation on the nutritional, sensory, and gelatinization properties of colored brown rice varieties - Ziwei Xiao; Ziyu Wang; Congnan Zhang; Wei Xue; Xinxia Zhang; Ting Li; Juan Li; Cangliang Shen; Li Wang (Food Chemistry, 2025)

Elucidating flavor compounds in Chinese steamed bread via glutinous rice wine-fermented dough technique: A triangulated analysis combining electronic tongue, SPME-GC-MS, and quantitative descriptive analysis - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Bioscience, 2025)

Lysine functionalization regulates the electronic structure and reaction microenvironment of Cu2O for efficient and stable nitrite electroreduction - Xiao-Hui Wang; Yi-Ting Yang; Yue-Han Qin; Fan Yang; Yu Chen; Shu-Ni Li (Chemical Engineering Journal, 2025)

Microbial processes suppress antimony release during stibnite weathering under suboxic condition - Ting Lu; Li Shao; Aiwen Wu; Zengping Ning; Tangfu Xiao; Enzong Xiao (Chemical Geology, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Optimizing hematite reduction in high - Iron bauxite during Bayer process via bagasse: A path to efficient resource utilization - Xin He; Guo-zhi Lv; Xiao-lei Zhang; Qing-dong Li; Bing-shen Liu; Zhuang-zhuang Yun; Ting-an Zhang (Biomass and Bioenergy, 2025)

Intercropping sunflower with amaranth to remediate cadmium-contaminated agricultural land: performance and mechanism - Zhuo-hui Wu; Feifan Wang; Mai Ye; Jingru Zhang; Zhiyi Li; Yunrong Xi; Rongzhou Jin; Yanying Li; Zhipeng Chen; Ye Wu; Ting Huang; Qijie Cheng; et al. (Plant and Soil, 2025)

Palaeoenvironmental implications of Baiera hallei Sze from the Middle Jurassic in Shaanxi Province, China - Qing-Dan Zheng; Xiao-Ju Yang; Ting Li (Palaeoworld, 2025)

Constructing ligand-defective Z-scheme TiO2@NM-X heterojunction for photocatalytic degradation of indoor formaldehyde - Xin-yue Wei; Yong-yue Peng; Yi Liang; Wei Li; Jian Li; Song Liu; Xiao-ting Niu; Qunli Zhang (Journal of Environmental Chemical Engineering, 2025)

Particulate matter removal performance of basalt fiber fabric: Optimization on the textile structure and surface functionalization - Ming-Cheng Gao; Ting Zhao; Hui Li; Cun-Guang Liang; Xiao-Xi Cheng; Xin Jia; Peng-Cheng Ma (Journal of Environmental Chemical Engineering, 2025)

Purification, identification, and mechanism of action of novel antioxidant peptides from quinoa (Chenopodium quinoa wild.) protein hydrolysate - Huan-Huan Xiao; Xue-Ying Li; Ying-Ying Chen; Jin-Xiang Zhou; Ting Zhang; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Chemistry, 2025)

Black carp STAT2 enhances IRF3-mediated antiviral signaling by regulating its ubiquitination and improving its nuclear translocation - Yiru Huang; Xinyu Wang; Jinyi Li; Ting Li; Xiaoyu Liu; Ji Liu; Jun Xiao; Hui Wu; Yong'an Zhang; Hao Feng (Fish & Shellfish Immunology, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Inulin alleviates intestinal changes caused by gestational PFOA and GenX exposure in the offspring of mice through reshaping maternal gut microbiota and vertically inhibiting the TLR4/NF-κB/NLRP3 inflammatory pathway in the pups - Yu-Kui Chen; Ming-Quan Lai; Qin-Yao Zhang; Mei-Ting Zhong; Jin-Jin Zhang; Ya-Qi Chen; Xiao-Fan Guo; Qi Wang; Xiao-Li Xie (Environmental Pollution, 2025)

High performance CuxTi-NM with Cu-Ti catalytic pairs for the photocatalytic degradation of formaldehyde - Xin-yue Wei; Yi Liang; Shu-yuan Chen; Yong-yue Peng; Wei Li; Jian Li; Xiao-ting Niu; Wei Guo; Wen-tao Gan (Chemical Engineering Journal, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

Aporphine alkaloids and flavonoids from the roots of Fissistigma retusum (H. Lév.) Rehder - Ya-Ting Xiao; Xue-Na Zhao; Han Li; Ying Ren; Yu-Hang Liu; Yu-Ming Liu (Natural Product Research, 2025)

An SNP for the splice donor variant of i-type lysozyme 2 (lyz-i2) is associated with the resistance of Vibrio harveyi in Pacific white shrimp - Xin Zhang; Peng Luo; Chunhua Ren; Pengying Li; Yehui Tan; Hao Yang; Shuyang Wen; Bo Ma; Jiayue Yin; Yanhong Wang; Xiao Jiang; Jingxuan Liang; et al. (Aquaculture, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Dual-metal synergy in bismuth-porphyrin nanosheets for enhanced photo-Fenton degradation of ciprofloxacin - Xiao-Huan Liang; Xi Chen; Yuan Chen; Ao-Gang Liu; Ting Zhu; Zi-Tong Chen; Bao Li (Journal of Cleaner Production, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Identifying Immune Response Protein Biomarkers in Parkinson’s-Related Cognitive Impairment and Depression - Qiaozhen Su; Ting Lu; Yan Xu; Zhe Li; Hongfeng Liang; Chunye Zheng; Kunhong Li; Linshuang Ye; Zhixuan Ren; Dafeng Hu; Yan Huang; Lihua Zhu; et al. (Molecular Neurobiology, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Andrograpalides A–N, structurally diverse ent-labdane diterpenoids with anti-inflammatory activities from the leaves of Andrographis paniculata - Xiao Zhang; Yan-Zhen Li; Ya-Ting Lai; Wei Zeng; Min Yu; Jun-Tao Huang; Hong-Lei Jin; Wei-Qun Yang; Zhong-Xiang Zhao (Phytochemistry, 2025)

Corrigendum to “Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes” [J Hazard Mater 489 (2025) 137706] - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Two magmatic-hydrothermal events in Xinzhai Sn polymetallic deposit, Yunnan Province, China: Constraints from cassiterite U-Pb geochronology and elemental compositions of single fluid inclusions - Ying-Hua Chen; Wen-Chang Li; Ting-Guang Lan; Xiao-Yu Zhao; Ming-Guo Deng; Die Wang; Yan-Wen Tang; Ji-Huang Lai (Gondwana Research, 2025)

A green approach to CO2 capture using fly ash-based catalysts: Performance and mechanistic insights - Rui Zhang; Lianghong Zhou; Ting Li; Yingjie Niu; Haonan Liu; Ruqi Xiao; Chao’en Li; Francesco Barzagli (Fuel, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Mapping QTLs for adult-plant resistance to yellow rust in a hard winter wheat population Heyne × Lakin - Chunlian Li; Xiao-Ting Xu; Yibo Zhang; Shengjie Liu; Jianhui Wu; Dejun Han; Robert Bowden; John Fellers; Guihua Bai (Theoretical and Applied Genetics, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

Evolution of sexual dimorphism in nonhuman primates - Yuan-Ting Guo; Yijun Yang; Bolun Zhang; Hao Wu; Lei Wang; Baoguo Li; Christopher Opie; Xiao-Guang Qi (Science China Life Sciences, 2025)

P2X7 receptor is essential for ST36-attenuated cardiac fibrosis upon beta-adrenergic insult - Ting Zhang; Jing Lv; Zhong-yue Liu; Qiu-lian Lei; Ze-fei Jiang; Xiao-xiang Sun; Xing Yue; Xuan Li; Ke-li Zhu; Yun-kuan Yang; Ling Luo; Xin Cao (Purinergic Signalling, 2025)

NLRP3-Mediated PANoptosis and Associated Interventions in Endothelial Injury - Aiwei Yan; Ting Cao; Xiao Li; Xingchen Li; Chaochu Cui; Xianwei Wang (Cardiovascular Toxicology, 2025)

Research progress on electrochemiluminescence nanomaterials and their applications in biosensors - A review - Ming-Zhu Deng; Ming-Yu Zhong; Meng-Li Li; Gui-Qun Huang; Hao He; Xiao Xiao; Ruo-Bing Bai; Ruchika Hansanie Ukwatta; Li Mi; Ting-Ting Zhang; Yong-Hong Hu; Hui-Cheng Shi; et al. (Analytica Chimica Acta, 2025)

Isotopic disequilibrium of the retro-diffusive CO2 efflux affects photosynthetic C18OO discrimination and the estimation of mesophyll conductance - Sui Min Huang; Jérôme Ogée; Xiao Ying Gong; Wei Ting Ma; Lei Li; Xuming Wang; Hans Schnyder; Rudi Schäufele (Agricultural and Forest Meteorology, 2025)

Dracotangusions A and B, two new sesquiterpenes from Dracocephalum tanguticum Maxim. with anti-inflammatory activity - Ting-Ting Wang; Cheng-Peng Li; Yong-Sheng Wei; Zhao-Yue Dong; Fan-Cheng Meng; Min Chen; Xiao-Zhong Lan (Natural Product Research, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Not for nothing, microplastics can (potentially) reduce the risk of mosquito-to-human transmission of arboviruses - Jian-hang Li; Xiao-hui Liu; He-ting Gao; Guo-rui Liang; Teng Zhao; Chun-xiao Li (Journal of Hazardous Materials, 2025)

Microbial taxonomic diversity and functional genes mirror soil ecosystem multifunctionality in nonferrous metal mining areas - Meng-yao Zheng; Xiao-jun Qi; Zhi-yue Liu; Yi-ting Wang; Yan-bo Ren; Yuan Li; Yue Zhang; Bao-feng Chai; Tong Jia (Journal of Hazardous Materials, 2025)

Cd migration in water-level fluctuation zones of Three Gorges reservoir: Interactions of periphytic biofilms and tryptophan - Ting Liu; Mengting Xiao; Rongshan Du; Meng Li; Xinyi Li; Ying Xi; Yuanfei Lv; Honglin Liu; Yingping Huang; Tao Xu (Journal of Contaminant Hydrology, 2025)

Effects of pore structures of carbon paper on water management capability of a proton exchange membrane fuel cell - Yu-Ting Liu; Guo-Bao Huang; Xiao-Fang Zhang; Ting-Ting Yao; Li-Xia Cheng; Hong Zhu; Gang-Ping Wu (Fuel, 2025)

Removal performance and mechanism of Bi2O3 for radioactive iodine in water: The role of crystal forms and oxygen vacancy - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Concentration-dependent effects of polystyrene microplastics on methanogenic activity and microbial community shifts in sewer sediment - Lucheng Li; Ting Xiao; Zanji He; Qijin Chen (Bioresource Technology, 2025)

A silence catalyst: CCL5-mediated intercellular communication in cancer - Wei-Ting Hu; Ming Li; Pei-Jun Ma; Ding Yang; Xiao-Dong Liu; Yun Wang (Archives of Toxicology, 2025)

A dual-backbone lightweight detection and depth position picking system for multiple occlusions Camellia oleifera fruit - Shenping Xiao; Qianying Zhao; Yongzhong Chen; Ting Li (Computers and Electronics in Agriculture, 2025)

As(III) removal from drinking water using FMCTO@Fe3O4 in the adsorption-magnetic separation-sand filtration equipment: Trade-off between As removal efficiency and adsorbent utilization rate - Xue Bai; Yuyang Xiao; Kun Wu; Ting Liu; Zhihua Li (Water Research, 2025)

Mitigation of methane emissions from urban sewer sediments: Sulfate addition and freeze-drying treatment - Lucheng Li; Lu Xu; Ting Xiao; Zanji He; Qijin Chen (Process Safety and Environmental Protection, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Effects of early-life F-53B exposure on thyroid function in juvenile rats: The role of the cAMP signaling pathway - Shen-Pan Li; Wen-Hui Zhao; Jing Zhang; Wen-Ting Jiang; Jia-Yi Zhu; Yi-Xin Luo; Ping Xiang; Michael Bloom; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Ultrastructure and sense organs of ovipositors in the phytophagous gall-maker pest Ophelimus maskelli (Hymenoptera: Eulophidae) and its parasitoid, Closterocerus chamaeleon (Hymenoptera: Eulophidae) - Yuan-Hao Li; Yu-Yue Huang; Yu-Chun Huang; Xiao-Rong Tang; Wen-Ting Huang; Xia-Lin Zheng (Journal of Asia-Pacific Entomology, 2025)

Taxonomy of the subgenus Polistes (Polistella) Ashmead, 1904 from China, with a new species and an updated key (Hymenoptera: Vespidae: Polistinae) - Nan Xiao; Bin Chen; Ting-Jing Li (Journal of Asia-Pacific Entomology, 2025)

Effect of liquid nitrogen spray freezing conditions - temperature, sample volume and exposure depth - on the resulting temperature fluctuation, microstructure, and quality of large yellow croaker fish during frozen storage - Yuxiao Mao; Junde Ren; Hongyue Li; Hosahalli S. Ramaswamy; Ting Xiao; Sinan Zhang; Mingyun Dai; Tao Song; Yong Yu; Songming Zhu (Food Chemistry, 2025)

Chemical constituents of Ainsliaea fragrans and their chemotaxonomic significance - Xiao-Ting He; Yun-Na Wang; Xue-Mei Zhou; Jing-Jing Zhang; Xiao-Li Li; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Physiological, transcriptomic and metabolomic responses of the marine diatom Phaeodactylum tricornutum to the auxin IAA - Yu-Ting Chen; Dong-Sheng Zhao; Xiao-Li Liu; Huan Yang; Run-Ze Gu; Nan Li; Xiufeng Yan; Hui-Xi Zou (Algal Research, 2025)

Aeromagnetic Compensation Method Based on Recursive Least Square and Elastic Weight Consolidation - Xiao-Yu Ma; Jin-Sheng Zhang; Shou-Yi Liao; Ting Li; Ze-Hao Li (Applied Geophysics, 2025)

Organic fertilizer intensifies the vertical heterogeneity of DOM in paddy fields through interactions with soil minerals - Yi Xiao; Rong Huang; Weiliang Xiong; Binbin Liu; Qinghua Zhou; Tao Jiang; Vanessa N.L. Wong; Jiang Liu; Yingjie Wu; Youlin Luo; Qiquan Li; Qiang Xu; et al. (Soil and Tillage Research, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Biochar-algae microspheres based on sodium alginate for the highly efficient adsorption of malachite green dye: Kinetics, isotherms, and mechanism of adsorption - Wei-Zhe Wu; Rui Li; Zhi-Qian-Li Ma; Chun-Xiao Liu; Wen-Ting Zhao (Journal of Contaminant Hydrology, 2025)

Long-term study of Citrus changshan-huyou Y.B. Chang essential oil: Chemical transformations and their impact on antibacterial efficacy - Wenbin Xiao; Jiajing Guo; Yanjiao Fu; Zixuan Li; Tongping Zhang; Mingwang He; Ting Liu; Yangbo Xiao; Xuebo Shang; Fuhua Fu; Gaoyang Li; Donglin Su; et al. (Food Chemistry, 2025)

Exposure-effect of PFOS and PFOA on lung function: An integrated approach with epidemiological, cellular, and animal studies - Jia-Xin Zhou; Xiao-Di Qin; Xuan Liu; Wan-Ting He; Mohammed Zeeshan; Shyamali C. Dharmage; Jennifer Perret; Dinh Bui; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2025)

Microplastics reduced the natural attenuation of antibiotic resistance genes in fertilized soils - Jin-Tao Yang; Yu Zhang; Shi-Yu Xiong; Hai-Jing Wei; Wan-Ting Zhang; Xin-Lei Lian; Xiao-Li Xu; Hong-Xia Jiang; Jian Sun (Environmental Pollution, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Mycorrhizal growth and resource exchange define plant’s coexistence - Jiqiong Zhou; Pengsen Wang; Xiangjun Li; Li Wei; Yakov Kuzyakov; Yingying Su; Jianguo Zhang; Nan Huang; Lin Liu; Xinquan Zhang; Congyu Ma; Xiao Ma; et al. (Plant and Soil, 2025)

SIRT3 regulates PFKFB3-mediated glycolysis to attenuate cisplatin-induced ototoxicity both in vivo and in vitro - Wei Tang; Shimin Zong; Peiyu Du; Xuan Yu; Ting Li; Bo Liu; Yu Zhong; Wenyang Lei; Wenting Yu; Hongjun Xiao (Archives of Toxicology, 2025)

Protective Effect of Lycium Barbarum Polysaccharides and Sodium Selenite on Cadmium Chloride–Induced Testicular Toxicity in Rats - Xueling Zhang; Yongxin Zhang; Ting Wang; Deng Xiao; Jianding Wang; Chao Ma; Tong Liu; Duoming Zhao; Sheng Li; Junling Wang; Chengyun Li (Biological Trace Element Research, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Characterization of the ribosomal RNA methylase gene erm(A) and its promoter mutation in Campylobacter coli from chicken cecum - Ting Liu; Xiao Liu; Xingyang Dai; Jinhu Huang; Runsheng Li; Liping Wang; Xiaoming Wang (International Journal of Food Microbiology, 2025)

Effect of lactic acid on short-chain fatty acids and hydrogen production during anaerobic fermentation of acidified food waste - Xudong Wang; Xujia Ming; Xiao Han; Yao Liu; Mengyu Chen; Ting Zhang; Xianguo Li; Dahai Zhang (Fuel, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

A Rare Patient of SEZ6L2 Antibody–Associated Cerebellar Ataxia - Chen-hui Cao; Wen-li Li; Yao Zhang; Ting Wei; Chun-lin Yang; Xiao-li Li; Bin Liu (The Cerebellum, 2025)

Responses of zebrafish to chronic environmental stressors: anxiety-like behavior and its persistence - Xiao-hong Li; Cheng Fu; Xue-ting Tan; Shi-jian Fu (Frontiers in Marine Science, 2025)
Introduction Fish in natural ecosystems face long-term environmental stressors, with anxiety being a critical stress response. This study investigates how chronic stressors—predators, social isolation, and caffeine—affect anxiety-like behavior and cortisol levels in zebrafish ( Danio rerio ), and examines the persistence of these effects post-stressor removal. Methods Zebrafish were exposed to three stressors for 14 days. Anxiety-like behavior and cortisol levels were measured for up to 28 days following the removal of the stressors. Results Chronic predator stress significantly increased anxiety-like behavior and cortisol levels, persisting for at least seven days post-removal. Social isolation reduced anxiety-like behavior and cortisol levels, with effects lasting no less than one day after re-socialization. Caffeine induced temporary anxiolytic effects, reversing one day post-withdrawal and persisting for at least seven days, while cortisol levels remained elevated. Discussion Zebrafish exhibit stressor-specific behavioral and physiological changes with varying persistence. These findings enhance understanding of fish responses to environmental stressors, offering insights into their survival strategies and ecosystem health.

Replication factor C4, which is regulated by insulin-like growth factor 2 mRNA binding protein 2, enhances the radioresistance of breast cancer by promoting the stemness of tumor cells - Xiao-Yu Zhu; Pi-Song Li; Hui Qu; Xing Ai; Zi-Ting Zhao; Jia-Bei He (Human Cell, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

Herbaceous competition does not affect positive tree diversity effects on seedling crown complementarity - Muhammad Abdullah; Li-Ting Zheng; Li Zhang; Bai-Yu Yang; Xiao-Chen Fang; Di-Feng Bao; Samreen Ghulam Rasool; Ci-Liang Zhao; En-Rong Yan (Forest Ecology and Management, 2025)

Efficacy and application potential of purified hydrocolloid coatings sprayed onto maize seeds subjected to anti-aging - Lin Zhang; Shi-Chao Yuan; Tai-Yue Wang; Xiang-Yang Wang; Xiao-Di Hao; Li-Ting Hao; Chen Shi (Environmental Research, 2025)

Short-term electrical load forecasting based on pattern label vector generation - Haozhe Zhu; Qingcheng Lin; Xuefeng Li; Hui Xiao; Ting Shao (Energy and Buildings, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Biochar enhanced co-composting for peat-free seedling substrate: A win-win solution for sustainable development of modern vegetable industry - Xiaoxia Fan; Yiyuan Wei; Dan Song; Ting Zhou; Ronghua Li; Xiaoxuan Su; Tao Zhang; Shang Cheng; Ran Xiao (Process Safety and Environmental Protection, 2025)

Treatment of dye-containing wastewater using discarded animal blood-derived hemoglobin crystals - Xiao-Qian Jin; Jie Liu; Chen-Yuan Li; Liang-Liang Chen; Jia-Lei Li; Xue-Ting Wang; Guang-Ming Mi; Da-Chuan Yin (Journal of Environmental Management, 2025)

Double enzyme enhanced microbial induction of carbonate precipitation (E-MICP) to improve mechanical properties of sandy soil and its biocementation mechanism - Lei Niu; Yao-ting Duan; Xin Xu; Xiao-yan Wu; Zhe Wang; Chun-li Zheng (Journal of Environmental Chemical Engineering, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Enhancing electrochemical performance in sodium-ion batteries: Strategic modification of oxygen-containing functional groups in hard carbon - Yulong Li; Yin Yang; Rundan Lin; Chen Zhang; Ting Xiao; Zhuang Ma; Qi Zhang; Xinlong Ma (Fuel, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Lactiplantibacillus plantarum DACNJS22 alleviates benzo(a)pyrene-induced neurobehavioral injury in mice: Insights from gut microbiota and short-chain fatty acids - Yu-Hang Jiang; Yang-You Li; Wei-Gang Xin; Yu-Ting Zhao; Xiao-Yong Chen; Jia-Jia Song; Chen Wang; Hua-Yi Suo (Food Bioscience, 2025)

A comprehensive analysis-based study of Di-(2-ethylhexyl) phthalate (DEHP)—Environmental explanation of bladder cancer progression - Fei Lin; Wen-Cai Zheng; Zhi-Bin Ke; Dong-Ning Chen; Yu-Ting Xue; Yun-Zhi Lin; Xiao-Dong Li; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Ning Xu (Environmental Pollution, 2025)

From the perspective of photo-induced holes lifetime: Application of anionic and cationic co-embedded carbon nitride in marine - Wanfeng Li; Ting Shen; Xiao Wang; Jiaping Wang; Zheng Xing; Faqian Liu; Weihua Li (Chemical Engineering Journal, 2025)

Dorsal CA1 NECTIN3 Reduction Mediates Early-Life Stress-Induced Object Recognition Memory Deficits in Adolescent Female Mice - Yu-Nu Ma; Chen-Chen Zhang; Ya-Xin Sun; Xiao Liu; Xue-Xin Li; Han Wang; Ting Wang; Xiao-Dong Wang; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2025)

The interactive effect of extreme weather events and PM2.5 on respiratory health among the elderly: a case-crossover study in a high-altitude city - Zhenxu Ning; Yanjun Ma; Shuzhen He; Genshan Li; Ting Xiao; Chunguang Ma; Jing Wu (International Journal of Biometeorology, 2025)

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Grazing increases the complexity of networks and ecological stochastic processes of mycorrhizal fungi - Jiqiong Zhou; Pengsen Wang; Li Wei; Jianguo Zhang; Xuxu Li; Nan Huang; Gang Liu; Kun Zou; Rui Fan; Lin Liu; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2025)

Formation and resuscitation of viable but non-culturable (VBNC) yeast in the food industry: A review - Yang Xiao; Jiayang Wang; Pengdong Sun; Ting Ding; Jingyuan Li; Yang Deng (International Journal of Food Microbiology, 2025)

Effects of UV-A irradiation and microbial fermentation on the physicochemical, microstructure and functional properties of okara - Ya-Ting Lei; Fan-Bing Meng; Xiao-Lei Jiao; Yuan-Mou Tang; Qi-Jun Wu; Yun-Cheng Li (Food Research International, 2025)

One-step cascade amplification system based on entropy-driven catalysis and DNAzyme triggered DNA walker for label-free detection of acetamiprid - Li Yang; Hao Lu; Xuemei Zhang; Li Zhu; Xiaoli Xiong; Ting Xiao; Liping Zhu (Food Chemistry, 2025)

Incorporating graphene quantum dots boosts thermoelectric performance of PEDOT:PSS films - Ting Wu; Xiao-Lei Shi; Yu-Yu Deng; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Fang Yue; Pei Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2025)

Overexpression of PtNRPS1 enhances diatom-mediated bioremediation of salicylate pollution - Dong-Sheng Zhao; Yu-Ting Chen; Jia-Min Xu; Xiao-Li Liu; Yi-Cheng Xu; Peng Cao; Junliang Li; Shengqin Wang; Nan Li; Yong Li; Shu-Ming Li; Xiufeng Yan; et al. (Bioresource Technology, 2025)

Effects of imidacloprid on Orius similis: assessing growth, development, and reproduction through age-stage two-sex life table analysis under contact and stomach toxicity treatments - Bo Zhang; Yi-Ru Li; Jin-Long Zhang; Guo-Hua Chen; Nian Yang; Ji-Huan Liu; Guo-Ting Yuan; Xiao-Ming Zhang (Journal of Pest Science, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Construction of label-free electrochemical aptasensor and logic circuit based on triple-stranded DNA molecular switch - Ya Zhou; Li Yang; Xuemei Zhang; Li Zhu; Xiaoli Xiong; Ting Xiao; Liping Zhu (Analytica Chimica Acta, 2025)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Impact of metals exposure on lung function and serum club cell secretory protein among schoolchildren: A mixture and mediation analysis - Jie Li; Meili Shen; Ting Wang; Xiao Zhang; Wen Gu; Mengmeng Xu; Tongjin Yang; Jie Cui; Xin Xia; Guoping Chen; Siyu Zheng; Haoying Yang; et al. (Journal of Hazardous Materials, 2024)

Effect of inoculation with different Eurotium cristatum strains on the microbial communities and volatile organic compounds of Fu brick tea - Yu Xiao; Hui Chen; Yulian Chen; Chi-Tang Ho; Yuanliang Wang; Ting Cai; Shi Li; Jinrong Ma; Tianyang Guo; Liang Zhang; Zhonghua Liu (Food Research International, 2024)

Inulin alleviates GenX-induced intestinal injury in mice by modulating the MAPK pathway, cell cycle, and cell adhesion proteins - Qin-Yao Zhang; Ming-Quan Lai; Yu-Kui Chen; Mei-Ting Zhong; Min Gi; Qi Wang; Xiao-Li Xie (Environmental Pollution, 2024)

High-performance thermoelectric PEDOT:PSS fiber bundles via rational ionic liquid treatment - Yu-Yu Deng; Xiao-Lei Shi; Ting Wu; Hao Wu; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Pei Huang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Functional diversification of contact calls contribute to the cohesion of a multi-level society - Yi-Jun Yang; Ying Yan; Gu Fang; Yu-Ting Song; Jing Zang; Wen-Yong Tian; Dai-Bo Zhu; Paul A. Garber; Bao-Guo Li; Xiao-Guang Qi (Behavioral Ecology and Sociobiology, 2024)

Bushen Huoxue acupuncture ameliorates Alzheimer’s disease by upregulating MARCHF3 to induce NLRP3 ubiquitination and inhibit caspase-1-dependent pyroptosis - Hong Zhu; Ting Zhang; Ruomeng Li; Dan Ren; Jiangxi Xu; Lan Xiao (Metabolic Brain Disease, 2024)

High emission of black carbon in heavy-duty diesel vehicles: Insights from microscopic operating conditions - Ting Chen; Xiao He; Liqiang He; Yan You; Lewei Zeng; Mingqiu Gao; Fengbin Wang; Yihuan Cao; Zhenhua Li; Xuan Zheng; Shaojun Zhang; Guangyi Xu; et al. (Science of The Total Environment, 2024)

A molecular mechanism underlies grass carp (Ctenopharyngodon idella) TARBP2 regulating PKR-mediated cell apoptosis - Miao-miao Li; Chang-bai Tao; Mei-feng Li; Chu-xin Wu; Ting-ting Yu; Zhi-qing Feng; Qing-Zhang; Ze-yin Jiang; Hui-ling Mao; Shang-hong Wang; Xiao-wen Xu; Cheng-yu Hu (Fish & Shellfish Immunology, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Tunable sulfur vacancies in amorphous-crystalline AC-Bi2S3-x@C derived from CAU-17 for efficient capture of radioiodine: Comparison of sulfur vacancies in amorphous and crystalline structures - Kai-Wei Chen; Xin-Yu Zhou; Yi-Ting Chen; Xiao-Jun Dai; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ping Mao; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2024)

Acute toxicity of salicylic acid and its derivatives on the diatom Phaeodactylum tricornutum: Physico-Biochemical and transcriptomic insights - Dong-Sheng Zhao; Muhammad Ahsan Farooq; Min Li; Yu-Ting Chen; Jia-Min Xu; Xiao-Li Liu; Aiqin Zhang; Xiufeng Yan; Hui-Xi Zou; Qiuying Pang (Aquatic Toxicology, 2024)

Understanding the mechanisms and potential pathways of soil carbon sequestration from the biogeochemistry perspective - Xiaojuan Feng; Guohua Dai; Ting Liu; Juan Jia; Erxiong Zhu; Chengzhu Liu; Yunpeng Zhao; Ya Wang; Enze Kang; Jun Xiao; Wei Li (Science China Earth Sciences, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Oxygen evolution reaction enhancing electrochemical performance of V-doped Ni(OH)2 for aqueous asymmetric supercapacitors - Ting Xiao; Hongxiang Lin; Can Tang; Xiuru Li; Yuting Mei; Lin Gao; Lihua Jiang; Peng Xiang; Shibing Ni; Yequan Xiao; Xinyu Tan (Chemical Engineering Journal, 2024)

UV light absorption at 370 nm by mineral dust, organic carbon, and elemental carbon in the Himalayas and Tibetan Plateau - Chong-Shu Zhu; Yao Qu; Yue Zhou; Nan Wang; Hong Huang; Ting Zhang; Xiao-Li Su; Jun-Ji Cao (Atmospheric Environment, 2024)

Thalamic Nucleus Reuniens Glutamatergic Neurons Mediate Colorectal Visceral Pain in Mice via 5-HT2B Receptors - Di Li; Han Du; Shu-Ting Qu; Jing-Lai Wu; Yong-Chang Li; Qi-Ya Xu; Xia Chen; Xiao-Xuan Dai; Ji-Tian Xu; Qian Wang; Guang-Yin Xu (Neuroscience Bulletin, 2024)
Irritable bowel syndrome (IBS) is a common functional bowel disorder characterized by abdominal pain and visceral hypersensitivity. Reducing visceral hypersensitivity is the key to effectively relieving abdominal pain in IBS. Increasing evidence has confirmed that the thalamic nucleus reuniens (Re) and 5-hydroxytryptamine (5-HT) neurotransmitter system play an important role in the development of colorectal visceral pain, whereas the exact mechanisms remain largely unclear. In this study, we found that high expression of the 5-HT 2B receptors in the Re glutamatergic neurons promoted colorectal visceral pain. Specifically, we found that neonatal maternal deprivation (NMD) mice exhibited visceral hyperalgesia and enhanced spontaneous synaptic transmission in the Re brain region. Colorectal distension (CRD) stimulation induced a large amount of c-Fos expression in the Re brain region of NMD mice, predominantly in glutamatergic neurons. Furthermore, optogenetic manipulation of glutamatergic neuronal activity in the Re altered colorectal visceral pain responses in CON and NMD mice. In addition, we demonstrated that 5-HT 2B receptor expression on the Re glutamatergic neurons was upregulated and ultimately promoted colorectal visceral pain in NMD mice. These findings suggest a critical role of the 5HT 2B receptors on the Re glutamatergic neurons in the regulation of colorectal visceral pain.

Correction: Edaravone Maintains AQP4 Polarity Via OS/MMP9/β-DG Pathway in an Experimental Intracerebral Hemorrhage Mouse Model - Zhenhua Wang; Yuan Li; Zhixu Wang; Yuhui Liao; Qingqing Ye; Shilong Tang; Ting Wei; Pengyu Xiao; Juan Huang; Weitian Lu (Molecular Neurobiology, 2024)

Plasmalogens and Octanoylcarnitine Serve as Early Warnings for Central Retinal Artery Occlusion - Chuansen Wang; Ying Li; Jiaqing Feng; Hang Liu; Yuedan Wang; Yuwei Wan; Mengxue Zheng; Xuejie Li; Ting Chen; Xuan Xiao (Molecular Neurobiology, 2024)
Central retinal artery occlusion (CRAO) is a kind of ophthalmic emergency which may cause loss of functional visual acuity. However, the limited treatment options emphasize the significance of early disease prevention. Metabolomics has the potential to be a powerful tool for early identification of individuals at risk of CRAO. The aim of the study was to identify potential biomarkers for CRAO through a comprehensive analysis. We employed metabolomics analysis to compare venous blood samples from CRAO patients with cataract patients for the venous difference, as well as arterial and venous blood from CRAO patients for the arteriovenous difference. The analysis of metabolites showed that PC(P-18:0/22:6(4Z,7Z,10Z,13Z,16Z,19Z)), PC(P-18:0/20:4(5Z,8Z,11Z,14Z)) and octanoylcarnitine were strongly correlated with CRAO. We also used univariate logistic regression, random forest (RF), and support vector machine (SVM) to screen clinical parameters of patients and found that HDL-C and ApoA1 showed significant predictive efficacy in CRAO patients. We compared the predictive performance of the clinical parameter model with combined model. The prediction efficiency of the combined model was significantly better with area under the receiver operating characteristic curve (AUROC) of 0.815. Decision curve analysis (DCA) also exhibited a notably higher net benefit rate. These results underscored the potency of these three substances as robust predictors of CRAO occurrence.

Edaravone Maintains AQP4 Polarity Via OS/MMP9/β-DG Pathway in an Experimental Intracerebral Hemorrhage Mouse Model - Zhenhua Wang; Yuan Li; Zhixu Wang; Yuhui Liao; Qingqing Ye; Shilong Tang; Ting Wei; Pengyu Xiao; Juan Huang; Weitian Lu (Molecular Neurobiology, 2024)

High Homocysteine-Thiolactone Leads to Reduced MENIN Protein Expression and an Impaired DNA Damage Response: Implications for Neural Tube Defects - Baoling Bai; Chunlei Wan; Zonghui Xiao; Dan Li; Lingyun Liu; Kexin Zhang; Ting Zhang; Qin Zhang (Molecular Neurobiology, 2024)
DNA damage is associated with hyperhomocysteinemia (HHcy) and neural tube defects (NTDs). Additionally, HHcy is a risk factor for NTDs. Therefore, this study examined whether DNA damage is involved in HHcy-induced NTDs and investigated the underlying pathological mechanisms involved. Embryonic day 9 (E9) mouse neuroectoderm cells (NE4C) and homocysteine-thiolactone (HTL, active metabolite of Hcy)-induced NTD chicken embryos were studied by Western blotting, immunofluorescence. RNA interference or gene overexpression techniques were employed to investigate the impact of Menin expression changes on the DNA damage. Chromatin immunoprecipitation-quantitative polymerase chain reaction was used to investigate the epigenetic regulation of histone modifications. An increase in γH2AX (a DNA damage indicator) was detected in HTL-induced NTD chicken embryos and HTL-treated NE4C, accompanied by dysregulation of phospho-Atr-Chk1-nucleotide excision repair (NER) pathway. Further investigation, based on previous research, revealed that disruption of NER was subject to the epigenetic regulation of low-expressed Menin-H3K4me3. Overexpression of Menin or supplementation with folic acid in HTL-treated NE4C reversed the adverse effects caused by high HTL. Additionally, by overexpressing the Mars gene, we tentatively propose a mechanism whereby HTL regulates Menin expression through H3K79hcy, which subsequently influences H3K4me3 modifications, reflecting an interaction between histone modifications. Finally, in 10 human fetal NTDs with HHcy, we detected a decrease in the expression of Menin-H3K4me3 and disorder in the NER pathway, which to some extent validated our proposed mechanism. The present study demonstrated that the decreased expression of Menin in high HTL downregulated H3K4me3 modifications, further weakening the Atr-Chk1-NER pathway, resulting in the occurrence of NTDs.

One undescribed glycoside benzofuran derivative and a new p -hydroxybenzoate glycoside from the leaves of Illicium dunnianum Tutcher - Xiao-qing He; Hai-bo Li; Ting Li; Xin-yin Chen; Zhen-zhong Wang; Xin-sheng Yao; Wei Xiao; Yang Yu (Natural Product Research, 2024)

Municipal solid waste leachate treatment by three-stage membrane aeration biofilm reactor system - Xinglin Li; Ling Xiao; Xiaopeng Sui; Ming Li; Ning Wang; Zhiye Sun; Ting Li; Xiwei Cao; Baoan Li (Chemosphere, 2024)

Efficacy of novel anticoagulants derived from tick saliva in preventing hypercoagulation among post-acute COVID-19 patients - Dan Liao; Aaron Wei Liang Li; Cinthia Wan Ting Phua; Cheryl Xue Pei Chuah; Xiao Xun Yang; Tammy Xin Tian Low; Matthew Benson; Shoumo Bhattacharya; R. Manjunatha Kini; Mark Yan Yee Chan; Cho Yeow Koh (Toxicon, 2024)

BpAFP, a Broussonetia papyrifera latex chitinase, exhibits a dual role in resisting to both Verticillium wilt disease and lepidopterous pests, Plutella xylostella and Prodenia litura - Xianbi Li; Dan Jin; Feifei Yi; Meng Tang; Siyi Wan; Yanhua Fan; Yuehua Xiao; Ting Liu; Hui Li; Jiancong Li; Mingliang Qiu; Yan Pei (Plant Science, 2024)

Immunosuppressive leucosesterterpane and penta-nor-leucosesterterpane sesterterpenoids from Leucosceptrum canum - Ting-Ting Zhou; Man-Wen Zhang; Yan-Chun Liu; Xiao-Nian Li; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Non-target discovery and risk prediction of per- and polyfluoroalkyl substances (PFAS) and transformation products in wastewater treatment systems - Ting Liu; Li-Xin Hu; Yu Han; Sheng Xiao; Liang-Li Dong; Yuan-Yuan Yang; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Journal of Hazardous Materials, 2024)

A novel nitric oxide-driven nanomotor for synergistic treatment of ischaemic stroke: Enhanced deep brain penetration and therapeutic efficacy - Zhicheng Xiao; Yi Li; Ting Chen; Chenchen Xie; Jun Liao; Pu Lin; Zhe-Sheng Chen; Yan Qiu; Jian Cai; Chuan Zhang; Tingfang Wang (Chemical Engineering Journal, 2024)

Ultrasound probe enhanced enzymatic hydrolysis for rapid separation of β2-adrenergic agonists from animal urine and livestock wastewater: Applicability to biomonitoring investigation - Zhiming Xiao; Yinji Jin; Ying Cao; Ting Yao; Yao Fu; Decheng Suo; Shi Wang; Gang Chen; Xinxue Zhao; Runxian Li; Xia Fan (Analytica Chimica Acta, 2024)

Effect of dietary krill oil levels on the regulation of ovary development in Pacific white shrimp (Litopenaeus vannamei) broodstock - Xiaolong Liang; Chang Xu; Ping Wang; Tong Chang; Xianming Xiao; Ting Li; Fenglu Han; Erchao Li (Aquaculture, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Robust and tunable hydrogels strengthened by dynamic amphiphilic ionic domains - Wenzhe Xiao; Ting He; Wanting Zhao; Wenjin Li; Yichen Liu; Cheng Li; Qizhen Luo; Weidong Zhao; Jipeng Yan; Jian Sun (Chemical Engineering Journal, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

TBC1D10B promotes tumor progression in colon cancer via PAK4‑mediated promotion of the PI3K/AKT/mTOR pathway - Xiao-Jv Chi; Yi-Bei Song; Haoran Zhang; Li-Qiang Wei; Yong Gao; Xue-Jing Miao; Shu-Ting Yang; Chun-Yu Lin; Dong Lan; Xiquan Zhang (Apoptosis, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

Sulfur vacancy-rich bismuth sulfide nanowire derived from CAU-17 for radioactive iodine capture in complex environments: Performance and intrinsic mechanisms - Kai-Wei Chen; Xin-Yu Zhou; Xiao-Jun Dai; Yi-Ting Chen; Shu-Xuan Li; Chun-Hui Gong; Peng Wang; Ping Mao; Yan Jiao; Kai Chen; Yi Yang (Journal of Hazardous Materials, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Viscoelastic cues to induce stem cell migration and neuronal differentiation in cell-free hydrogel-assisted TBI recovery - Xiaoyin Liu; Chengheng Wu; Yusheng Zhang; Gaowei Li; Suping Chen; Zhihong Chen; Peng Liu; Kai Wu; Xiaoyang Wu; Ting Zhou; Mingze Zeng; Zi Qiao; et al. (Chemical Engineering Journal, 2024)

Genome-wide association studies dissect low-phosphorus stress response genes underling field and seedling traits in maize - Bowen Luo; Guidi Zhang; Ting Yu; Chong Zhang; Guohui Yang; Xianfu Luo; Shuhao Zhang; Jianyong Guo; Haiying Zhang; Hao Zheng; Zirui Tang; Qile Li; et al. (Theoretical and Applied Genetics, 2024)

Effect of plasma activated water Immersion on Broccoli Seed Germination and Nutritional Quality of Sprouts - Gongheng Che; Ting Jiang; Xiaodan Li; Junxia Xiao; Liang Liu; Jianteng Wei; Liping Guo (Journal of Plant Growth Regulation, 2024)

A key hub for climate systems: deciphering from Southern Ocean sea surface temperature variability - Ninghong Li; Xufeng Zheng; Ting Su; Xiao Ma; Junying Zhu; Dongdong Cheng (Frontiers in Marine Science, 2024)
The Southern Ocean connects the Pacific, Atlantic, and Indian Oceans, serving as a key hub for the global overturning circulation. The climate of the Southern Ocean is closely linked to the low-latitude equatorial Pacific, as well as the high-latitude regions of the North Atlantic, making it an important component of the global climate system. Due to the interactions of various processes such as atmospheric, oceanic, and ice cover, the Southern Ocean exhibits a complex and variable sea surface temperature structure. Satellite observations indicate that since 1980, the sea surface temperature of the Southern Ocean has been cooling, contrary to the global warming trend. However, due to the relatively short length of satellite observations, the specific mechanisms are not yet clear. Here, we used the EOF method to analyze sea surface temperature data since 1870 (HadISST1 and ERSSTV5), with three main separated modes explaining over 70% of the sea temperature variability. Among them, the first mode shows widespread positive sea surface temperature anomalies in the Southern Ocean, with a time series change consistent with global temperature anomalies, representing a mode of global warming. The second mode corresponds to the Atlantic Multidecadal Oscillation (AMO) but with a lag of approximately 4 years. The third mode is consistent with the variability of the El Niño-Southern Oscillation (ENSO). Furthermore, our study indicates that despite the ongoing global warming since 1980, the negative phase of AMO and positive phase of ENSO may counteract the effects of global warming, leading to an overall cooling trend in the sea surface temperature of the Southern Ocean.

Coating seeds with biopolymers extracted from waste-activated sludge - Chen Shi; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Shi-Ming Su; Zhongfang Lei; Xiao-Di Hao (Sustainable Chemistry and Pharmacy, 2024)

Non-target and target screening and risk assessment of per- and polyfluoroalkyl substances in textile wastewater and receiving river - Sheng Xiao; Ting Liu; Li-Xin Hu; Bin Yang; Guang-Guo Ying (Science of The Total Environment, 2024)

Partially knocking out NtPDK1a/1b/1c/1d simultaneously in Nicotiana tabacum using CRISPR/CAS9 technology results in auxin-related developmental defects - Qian-Wei Ren; Tian-Yao Liu; Hu-Jiao Lan; Zhen-Chao Li; Min-Jun Huang; Ya-Ting Zhao; Yu Chen; Li-Na Liao; Xiao-Han Ma; Jian-Zhong Liu (Plant Science, 2024)

Berberine hydrochloride delays citrus sour rot mainly by disrupting carbohydrate and energy metabolism of Geotrichum citri-aurantii spores - Lu Li; Bo Lin; Yu Ting; Maohui Li; Jinjin Hu; Jingjing Song; Yingjuan Yan; Jiaxin Chen; Hong Xiao; Nengguo Tao (Pesticide Biochemistry and Physiology, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Salinity-mediated enhancement of quaternary ammonium compounds resistance and removal in endophytic bacteria LSE01 - Xiao Xiao; Junjie Li; Xiaotong Wang; Lin Ding; Shengju Shen; Ting Liu; Zhong Ren; Xubiao Luo (Environmental Research, 2024)

Synergistic effect between p-n heterojunction and oxygen vacancies of Co3O4-C/Fe-MOF for highly sensitive detection of trace atrazine - Hui Shu; Tingrun Lai; Bo Yao; Mengyao Li; Haoyu Li; Shanli Wang; Ting Chen; Xuechun Xiao; Yude Wang (Chemical Engineering Journal, 2024)

High capacity and long service in sodium-ion batteries achieved by the refinement of BiOCl from lamellar to flower-like in ether electrolyte - Sheng-Li Wei; Yan-Ling Yang; Xiao-Lei Shi; Yu Sun; Jin-Geng Chen; Xue-Feng Tian; Yuan-Ting Wu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Characteristics and influencing factors of CO2 emission from inland waters in China - Ting Zhou; Xiaofeng Wang; Zuolin Xiao; Zhaoyin Qing; Xianxiang Li; Jilong Wang; Ziyi Que (Science China Earth Sciences, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

Discovery of HNPC-A188: a novel acaricide containing trifluoroethyl thioether and pyrimidin-4-amine - Ting Xiao; Aiping Liu; Xingping Liu; Fujun Zhong; Guojun Li; Zhichang Huang; Zai Zhang; Yeguo Ren; Jiang-Sheng Li; Weidong Liu (Medicinal Chemistry Research, 2024)

Soil physicochemical properties and plant functional traits regulate ecosystem multifunctionality of alpine grassland under different livestock grazing assemblies - Bin Feng; Yu-Zhen Liu; Wen-Ting Liu; Wei-Dong Lv; Cai-Cai Sun; Zeng-Zeng Yang; Cai-Di Li; Qin-Yuan Zhou; Fang-Cao Wang; Xiao-Xia Yang; Quan-Min Dong (Agriculture, Ecosystems & Environment, 2024)

A Four Amino Acid Metabolism-Associated Genes (AMGs) Signature for Predicting Overall Survival Outcomes and Immunotherapeutic Efficacy in Hepatocellular Carcinoma - Lu-sheng Liao; Zi-jun Xiao; Jun-li Wang; Ting-jun Liu; Feng-die Huang; Yan-ping Zhong; Xin Zhang; Ke-heng Chen; Run-lei Du; Ming-you Dong (Biochemical Genetics, 2024)

Coastal hypoxia response to the coupling of catastrophic flood, extreme marine heatwave and typhoon: a case study off the Changjiang River Estuary in summer 2020 - Xiao Ma; Qicheng Meng; Dewang Li; Yuanli Zhu; Xiaobo Ni; Dingyong Zeng; Di Tian; Ting Huang; Zhihao Jiang; Haiyan Jin; Feng Zhou (Acta Oceanologica Sinica, 2024)

Evolutionary ecology of denitrifying methanotrophic NC10 bacteria in the deep‐sea biosphere - Yingdong Li; Ting Wang; Hongmei Jing; Yao Xiao (Molecular Ecology, 2024)
The NC10 phylum links anaerobic methane oxidation to nitrite denitrification through a unique O 2 ‐producing intra‐aerobic methanotrophic pathway. Although numerous amplicon‐based studies revealed the distribution of this phylum, comprehensive genomic insights and niche characterization in deep‐sea environments were still largely unknown. In this study, we extensively surveyed the NC10 bacteria across diverse deep‐sea environments, including waters, sediments, cold seeps, biofilms, rocky substrates, and subseafloor aquifers. We then reconstructed and analysed 38 metagenome‐assembled genomes (MAGs), and revealed the extensive distribution of NC10 bacteria and their intense selective pressure in these harsh environments. Isotopic analyses combined with gene expression profiling confirmed that active nitrite‐dependent anaerobic methane oxidation (n‐DAMO) occurs within deep‐sea sediments. In addition, the identification of the Wood–Ljungdahl (WL) and 3‐hydroxypropionate/4‐hydroxybutyrat (3HB/4HP) pathways in these MAGs suggests their capability for carbon fixation as chemoautotrophs in these deep‐sea environments. Indeed, we found that for their survival in the oligotrophic deep‐sea biosphere, NC10 bacteria encode two branches of the WL pathway, utilizing acetyl‐CoA from the carbonyl branch for citric acid cycle‐based energy production and methane from the methyl branch for n‐DAMO. The observed low ratios of non‐synonymous substitutions to synonymous substitutions (pN/pS) in n‐DAMO‐related genes across these habitats suggest a pronounced purifying selection that is critical for the survival of NC10 bacteria in oligotrophic deep‐sea environments. These findings not only advance our understanding of the evolutionary adaptations of NC10 bacteria but also underscore the intricate coupling between the carbon and nitrogen cycles within deep‐sea ecosystems, driven by this bacterial phylum.

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

Lemon essential oil nanoemulsions: Potential natural inhibitors against Escherichia coli - Wenbin Xiao; Zhipeng Gao; Ting Liu; Weiming Zhong; Sifan Jiang; Mingwang He; Fuhua Fu; Gaoyang Li; Donglin Su; Jiajing Guo; Yang Shan (Food Microbiology, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Synergistic improvement of humus formation in compost residue by fenton-like and effective microorganism composite agents - Jun Zhuo Cai; Ying Lan Yu; Zhan Biao Yang; Xiao Xun Xu; Guo Chun Lv; Chang Lian Xu; Gui Yin Wang; Xin Qi; Ting Li; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Bioresource Technology, 2024)

A sensitive and versatile electrochemical sensor based on hybridization chain reaction and CRISPR/Cas12a system for antibiotic detection - Xuemei Zhang; Li Zhu; Li Yang; Guoyu Liu; Shan Qiu; Xiaoli Xiong; Ke Huang; Ting Xiao; Liping Zhu (Analytica Chimica Acta, 2024)

Advanced “turn-on” colorimetric uranium platform based on the enhanced nanozyme activity of a donor-acceptor structured covalent organic framework - Sai Jin Xiao; Jing Huang; An Ting Qiu; Guang Zhou Liu; Li Zhang; Ting Wu; Ya Di Shi; Jian-Ding Qiu (Analytica Chimica Acta, 2024)

The mussel larvae microbiome changes in response to a temperature rise - You-Ting Zhu; Xiao Liang; Tian-Tian Liu; Deborah M. Power; Yi-Feng Li; Jin-Long Yang (Frontiers in Marine Science, 2024)
Ocean warming caused by global climate change influences the function, diversity, and community dynamics of commensal microorganisms, including the hemolymph and the gut microbiota in mussels. However, the microbiota in hard-shelled mussel ( Mytilus coruscus ) larvae and the effect of temperature on the microbial community structure have yet to be studied. Herein, we investigated the core microbiota of M. coruscus larvae and the impact of acute (4 h) and gradual (4 days) exposure to a rise in seawater temperature from 21 to 25 °C. Eleven core genera were identified in M. coruscus larvae by 16S rDNA gene sequencing: Alteromonas , Brevundimonas , Delftia , Microbacterium , Neptuniibacter , Neptunomonas , Pseudoalteromonas , Rhodococcus , Stenotrophomonas , Tenacibaculum , and Thalassotalea . The microbiota of larvae in the short exposure treatment was similar to the control. However, the abundance of Delftia , Neptunomonas , Pseudoalteromonadaceae , Rhodococcus , and Stenotrophomonas decreased significantly in the long-exposure larvae. In contrast, at the genus level, the abundance of Tenacibaculum increased significantly. Diversity and multivariate analyses confirmed that the microbiota patterns were linked to seawater warming over the long term. Microbiota diversity did not change significantly, regardless of whether the seawater temperature increased quickly or slowly; however, we observed a significant increase in the microbiota species abundance at higher temperatures. Among the altered bacterial genera, Delftia , Neptunomonas , and Rhodococcus function in the degradation of organic compounds; Pseudoalteromonas is closely associated with mussel attachment and metamorphosis, and Tenacibaculum is an opportunistic pathogen that can cause marine mollusk death. The results suggest that marine heat waves caused by climate change may reduce the ability of symbiotic bacteria to degrade environmental toxins, will affect mussel larvae metamorphosis, and increase the abundance of opportunistic pathogens, thereby increasing the risk of disease and death of mussel larvae.

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Transformation pathways of the carbon-containing group compounds during municipal sludge pyrolysis treatment - Tianxue Yang; Yi Xiao; Xin Zhao; Dongyang Li; Zhifei Ma; Wenxuan Li; Tiancheng Gong; Ting Zhang; Nannan Huang; Beidou Xi. (Waste Management, 2024)

Preparing a heavy-metal adsorbent based on alginate-like extracellular polymers from conventional activated sludge via polyethyleneimine grafting - Chen Shi; Run-Gen Zeng; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Xiao-Di Hao; Nan Zhang; Yuan-Yuan Wu (Sustainable Chemistry and Pharmacy, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

Study on the mechanism and stability of microbially induced struvite precipitation (MISP) for enhanced immobilization of uranium - Yao-ting Duan; Xin Xu; Lei Niu; Zhe Wang; Xiao-gang Huang; Chun-li Zheng (Journal of Cleaner Production, 2024)

TFN nanofiltration membrane incorporating ZIF-8@MXene for efficient removal ReO4- from simulated nuclear-contaminated wastewater - Ning-xiao Wei; Yu-xing Wang; Hua-li Chen; Li-guang Wu; Ting Wang (Journal of Environmental Chemical Engineering, 2024)

Construction of Co-ZIF-derived CoS2@Cu hollow heterogeneous nanotube array for the detection of hydrazine in environmental water samples - Lian Ou; Jie Yang; Li Xu; Shan Zhao; Xiaoli Xiong; Ting Xiao (Environmental Research, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Long non-coding RNA NONHSAT217600.1 is involved in the regulation of neodymium oxide-induced cytotoxicity in 16HBE cells - Jiaru Hong; Xietian Xiao; Ting Li; Huandong Wang; Qiuhan Hua (Molecular & Cellular Toxicology, 2024)

Genetically Predicted Apolipoprotein E Levels with the Risk of Panvascular Diseases: A Mendelian Randomization Study - Yi-Ming Shi; Dian Ou; Jia-Ting Li; Le Bao; Xiao-Dan Liu; Wei Zhang; Huang Ding (Cardiovascular Toxicology, 2024)

Characterization of multi-copy C3 genes and association analysis of C3.1 polymorphism with GCRV resistance traits in Ctenopharyngodon idella - Jia-yang Huang; Zhao Lv; Bin Li; Yan-rong Ying; Le Yang; Tiao-yi Xiao; Shu-ting Xiong (Aquaculture, 2024)

Functionally responsive hydrogels with salt-alkali sensitivity effectively target soil amelioration - Le Qi; Xiao Xiao; Ting Liu; Zhong Ren; Wei Ren; Qifeng Gao; Mengting Liu; Pangzhi Wei; Yongkang Lai; Weipeng Yao; Huanhuan An; Lan Zhang; et al. (Science of The Total Environment, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Transcriptomics combined with physiological analysis provided new insights into the Zn enrichment capacity and tolerance mechanism of Dendrobium denneanum Kerr - Yuanyuan Liu; Erya Xu; Yijun Fan; Linlong Xu; Jie Ma; Xuebing Li; Hui Wang; Siyu He; Ting Li; Yujiao Qin; Jingtao Xiao; Aoxue Luo (Plant Science, 2024)

LA-ICPMS in situ U Pb dating of skarn garnet from the Tongling ore district of eastern China - Ting Liang; Shao-Bing Zhang; Xiao-Yong Yang; Zhen-Xin Li; Xing-Yu Yao; Yu Wang; Sha-Sha Liu (Lithos, 2024)

Haze weather and mortality in China from 2014 to 2020: Definitions, vulnerability, and effect modification by haze characteristics - Zhou Yang; Jiangmei Liu; Jun Yang; Li Li; Ting Xiao; Maigeng Zhou; Chun-Quan Ou (Journal of Hazardous Materials, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

T-2 toxin induces mitochondrial dysfunction in chondrocytes via the p53-cyclophilin D pathway - Fang-fang Yu; Shui-yuan Yu; Lei Sun; Juan Zuo; Kang-ting Luo; Miao Wang; Xiao-li Fu; Feng Zhang; Hui Huang; Guo-yu Zhou; Yan-jie Wang; Yue Ba (Journal of Hazardous Materials, 2024)

Common vetch intercropping with reduced irrigation ensures potato production by optimizing microbial interactions - Ting Che; Xinyue Zhang; Mingyue He; Fei Wang; Na Li; Xiayun Zang; Zhuoliang Xiao; Yuanzhou Xu; Feng Hu; Yongfeng Ren; Huijuan Zhang; Li Xu; et al. (Field Crops Research, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

The Effect of Copper–Cadmium Co-Exposure and Hormone Remediation on the Ovarian Transcriptome of Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Liting Chen; Xin Yan; Jun Xiao; Zhirui Ma; Zhanyang Tang; Zhongbao Guo; Liping Li; Guixiang Tong; Honglian Tan; Fuyan Chen; Xinxian Wei; et al. (Fishes, 2024)
The escalating problem of copper (Cu) and cadmium (Cd) pollution in aquatic environments poses a significant threat to the ovarian tissue and reproductive capacity of fish, hindering the development of the aquaculture industry. However, the combined effects of Cu and Cd on fish gonadal development remain unclear. In this study, the fish species Nile tilapia was stressed with rearing water containing 300 μg/L Cu2+ and 100 μg/L Cd2+ for 30 days, followed by an intraperitoneal injection of luteinizing hormone-releasing hormone (LHRH-α) and human chorionic gonadotropin (HCG) at various concentrations. We investigated the ovarian transcriptome profiles before and after injection. Prior to injection, combined treatment with Cu and Cd resulted in reproductive dysfunction and metal ion imbalance in tilapia. Transcriptomic profiling revealed differential gene annotation concentrated in the MAPK signaling pathway and regulation of GTPase activity. Post-injection, all concentrations of LHRH-α and HCG groups showed an upregulated gonadosomatic index (G.S.I) and higher levels of vitellogenin (VTG), gonadotropin-releasing hormone (GnRH), gonadotropin (GTH), and estrogen (E2) in serum compared to the negative control group. Transcriptomic analysis revealed alterations in various ovarian signaling pathways, preliminarily revealing the in vivo molecular mechanisms and differences in LHRH-α and HCG. The findings from this study could help us better understand how to counteract the effects of combined Cu and Cd exposure on tilapia ovarian development, which has significant implications for the Nile tilapia aquaculture industry.

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

Molybdenum exposure induces inflammatory response via the regulatory effects of lncRNA-00072124/miR-308/OSMR crosstalk on JAK/STAT axis in duck kidneys - Wenjing Pu; Xuesheng Chu; Shiwen Xu; Xueyan Dai; Li Xiao; Ting Cui; Bingyan Huang; Guoliang Hu; Caiying Zhang (Science of The Total Environment, 2024)

Inulin alleviates perfluorooctanoic acid-induced intestinal injury in mice by modulating the PI3K/AKT/mTOR signaling pathway - Qin-Yao Zhang; Mei-Ting Zhong; Min Gi; Yu-Kui Chen; Ming-Quan Lai; Jing-Yi Liu; Yi-Ming Liu; Qi Wang; Xiao-Li Xie (Environmental Pollution, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Superior Photocatalytic Activity and Antibacterial Behavior of Chitosan-Anchored Ag/AgCl Composites - Xiao-fang Li; Ya-ting Zhou; Xiao-qiang Feng (Water, Air, & Soil Pollution, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Study on the trade-off/synergy between ecosystem services and human well-being based on land use in Weinan City, China - Zemin Ai; Yuyan Yao; Xiaohu Dang; Xinghua Li; Mengjia Hou; Yi Deng; Lie Xiao; Ting Li; Tao Wang (Environmental Science and Pollution Research, 2024)

Optimization of the adsorption performance of herbal residues as lanthanide ion-modified carriers for phosphate by fly ash and its application - Caigao Zhou; Zihan Chen; Guochun Lv; Changlian Xu; Guiyin Wang; Shirong Zhang; Zhanbiao Yang; Zhang Cheng; Junzhuo Cai; Ting Li; Yulin Pu; Zhien Pu; et al. (Chemosphere, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Gestational GenX and PFOA exposures induce hepatotoxicity, metabolic pathway, and microbiome shifts in weanling mice - Qin-Yao Zhang; Ling-Ling Xu; Mei-Ting Zhong; Yu-Kui Chen; Ming-Quan Lai; Qi Wang; Xiao-Li Xie (Science of The Total Environment, 2024)

Whole-body aging mediates the association between exposure to volatile organic compounds and osteoarthritis among U.S. middle-to-old-aged adults - Hao-long Zhou; Dong-sheng Di; Zhang-bo Cui; Ting-ting Zhou; Ting-ting Yuan; Qian Liu; Jian-li Zhang; Xiao Luo; Dan-yang Ling; Qi Wang (Science of The Total Environment, 2024)

Transgenerational effects of microplastics on Nrf2 signaling, GH/IGF, and HPI axis in marine medaka Oryzias melastigma under different salinities - Xiaolin Zhang; Xiao Chen; Lu Gao; Hai-Ting Zhang; Jiji Li; Yingying Ye; Qing-Ling Zhu; Jia-Lang Zheng; Xiaojun Yan (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Visible light-activated photosensitizer inhibits the plasmid-mediated horizontal gene transfer of antibiotic resistance genes - Yan-Zi Wang; Xin-Li An; Xiao-Ting Fan; Qiang Pu; Hu Li; Wen-Zhen Liu; Zhuo Chen; Jian-Qiang Su (Journal of Hazardous Materials, 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

Arbuscular mycorrhizae mitigate negative impacts of soil biodiversity loss on grassland productivity - Jiqiong Zhou; Yingying Su; Xiangjun Li; Yakov Kuzyakov; Pengsen Wang; Jinchao Gong; Xuxu Li; Lin Liu; Xinquan Zhang; Congyu Ma; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2024)

TBK1 upregulates the interferon response against virus by the TBK1-IRF3/7 axis in yellow catfish (Pelteobagrus fulvidraco) - Li-ming Xiong; Lei Zhang; Zhe Long; Xiang Zhao; Yan-rong Ying; Tiao-yi Xiao; Shu-ting Xiong (Fish & Shellfish Immunology, 2024)

The interaction between Fe and Co dual active sites for promoting ultra-sensitive detection of trace paraquat - Hui Shu; Tingrun Lai; Shanli Wang; Mengyao Li; Haoyu Li; Ting Chen; Xuechun Xiao; Yude Wang (Chemical Engineering Journal, 2024)

A low energy-consuming phase change absorbent of MAE/DGM/H2O for CO2 capture - Shumin Hong; Ting Li; Min Xiao; Teerawat Sema; Hongxia Gao; Zhiwu Liang (Chemical Engineering Journal, 2024)

An injectable selenite-containing hydrogel for synergistic tumor therapy by triggering ROS/RNS generation and disrupting NADPH homeostasis - Weiyong Tao; Xiaodan Wu; Jiaqi Li; Feige Wu; Chen Chen; Ting Jiang; Cunjing Xu; Shangtong Jiang; Jianglin Wang; Bo Xiao; Yingying Du; Shengmin Zhang (Chemical Engineering Journal, 2024)

Allicin ameliorates sepsis-induced acute kidney injury through Nrf2/HO-1 signaling pathway - Xiao-Jun Li; Ting Liu; Yuan Wang (Journal of Natural Medicines, 2024)
Acute kidney injury (AKI) is a complication that can be induced by different factors. Allicin is a class of organic sulfur compounds with anticancer and antibacterial effects, and has not been reported in sepsis-induced AKI (S-AKI). S-AKI was induced in c57BL/6 mice by cecal ligation puncture. In response to the treatment of allicin, the survival rate of mice with S-AKI was increased. Reduced levels of serum creatinine, blood urea nitrogen, UALB, KIM-1 and NGAL indicated an improvement in renal function of S-AKI mice. Allicin inhibited the inflammation and cell apoptosis, which evidenced by decreased levels of inflammatory cytokines and apoptosis-related proteins. Oxidative stress was evaluated by the levels of oxidative stress biomarkers, and suppressed by allicin. In addition, allicin-alleviated mitochondrial dysfunction was characterized by decreased JC-1 green monomer. These effects of allicin were also evidenced in HK2 cells primed with lipopolysaccharide (LPS). Both in vivo and in vitro experiments showed that the nuclear translocation of Nrf2 and the expression of HO-1 increased after allicin treatment, which was confirmed by ML385 and CDDO-Me. In summary, this study revealed the alleviating effect of allicin on S-AKI and demonstrated the promotive effect of allicin on nuclear translocation of Nrf2 for the first time. It was inferred that allicin inhibited the progression of S-AKI through Nrf2/HO-1 signaling pathway. This study makes contributions to the understanding of the roles of allicin in S-AKI.

Label-free fluorescence detection of human 8-oxoguanine DNA glycosylase activity amplified by target-induced rolling circle amplification - Mengxu Sun; Xiao Chen; Xiang Chen; Qianying Zhou; Ting Huang; Tong Li; Baoping Xie; Chunrong Li; Jin-Xiang Chen; Zong Dai; Jun Chen (Analytica Chimica Acta, 2024)

Transcriptome analysis of Iris japonica var. variegata for chlorophyll and photosynthesis-related pathways involved in white–green striped leaves - Xiaofang Yu; Linjie Yue; Qingling He; Shurui Li; Yunhao Zheng; Zhiwen Wang; Heting Wang; Rouzhi Liu; Xin Huang; Xue Xiao; Lijuan Yang; Ting Lei (Acta Physiologiae Plantarum, 2024)

Characteristics and potential human health risks of microplastics identified in typical clams from South Yellow Sea Mudflat - Qingyuan Guo; Cheng Ding; Zhaoxia Li; Xiao Chen; Jinling Wu; Xuan Li; Jianwei Yu; Chunmiao Wang; Feng Liang; Ting Chen; Bairen Yang; Tianming Chen (Science of The Total Environment, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

In vitro gastrointestinal digestion of thermally reversible and irreversible fish gelatin induced by microbial transglutaminase - Xiao-Mei Sha; Ting Fang; Jia-Hui Zhang; Sheng Shu; Wen-Li Jiang; Zi-Zi Hu; Zong-Cai Tu (Food Hydrocolloids, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Metabolome and Transcriptome Association Analysis Reveals the Link Between Pigmentation and Nutrition Utilization in the Juveniles of Sea Cucumber Holothuria leucospilota - Jiasheng Huang; Zixuan E; Wenjie Pan; Zhi Li; Tiehao Lin; Chunhua Ren; Peng Luo; Bo Ma; Yang Liu; Xugan Wu; Chaoqun Hu; Xiao Jiang; et al. (Marine Biotechnology, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Multifunctional platinum-tellurium nanorods modified with hyaluronic acid remove reactive oxygen species to improve the photothermal treatment of rheumatoid arthritis - Meng-Wen Ma; Kai-Lin He; Chao-Qing Li; Xiao-Ting Xie; Sui Zhou; Bin Zhang; Xiao-Lin Hou; Cheng Li; Yuan-Di Zhao; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2023)

Solvothermally silver doping boosting the thermoelectric performance of polycrystalline Bi2Te3 - Wen-Yi Chen; Xiao-Lei Shi; Qishuo Yang; Meng Li; Wanyu Lyu; Ting Liu; Tianyi Cao; Boxuan Hu; Weidi Liu; Shuai Sun; Yuanqing Mao; Matthew Dargusch; et al. (Chemical Engineering Journal, 2023)

High efficient alkaline hydrogen evolution catalyzed by W2COx-Ru composite system containing bridged oxygen - Yu Dai; Hong Chuan Fu; Xiao Hui Chen; Qing Zhang; Ting Li; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Targeted control of soil erosion through selective regulation of Eleocharis yokoscensis using mixed endophytes - Qifeng Gao; Xiao Xiao; Ting Liu; Zhong Ren; Wei Ren; Yunya Zhan; Wenqian Wang; Weiran Feng; Li Ma; Le Qi; Zixian Zhang; Xubiao Luo; et al. (CATENA, 2023)

Positive relationships between species diversity and genetic diversity on a local scale at Mt. Wu Yi, China - Lei Xie; YueYao Feng; Rong Zhao; Ting Lv; NingJie Wang; Yao Li; Xiao Zheng; ShuiFei Chen; Hui Ding; YanMing Fang (Biodiversity and Conservation, 2023)

Unraveling the genomic diversity and ecological potential of the genus Demequina: insights from comparative analysis of different saline niche strains - Lei Gao; Bao-Zhu Fang; Chun-Yan Lu; Kun-Hui Hong; Xin-Yu Huang; Ting-Ting She; Min Xiao; Wen-Jun Li (Frontiers in Marine Science, 2023)
During an investigation of the culturable microbial diversity of sediments with salinity from tidal flats and saline lake, seven strains of the genus Demequina were harvested. The genomic analysis and physiological characteristics of strains of this genus have unveiled their significant potential in degrading complex carbon source such as lignin, hemicellulose, chitin, and oligosaccharides. In addition, these strains show potential abilities in nitrite ammonification and sulfide oxidation. These findings not only improved our understanding of their metabolic model, but also provided valuable insights into their ecological roles. Four new species of the genus Demequina are described: Demequina litoralis sp. nov., with SYSU T00192 T designated as the type species; Demequina zhanjiangensis sp. nov., with SYSU T00b26 T as the type species; Demequina lignilytica sp. nov., with SYSU T00068 T as the type species; and Demequina muriae sp. nov., with EGI L300058 T as the type species. Additionally, strains SYSU T0a273, SYSU T00039-1, and SYSU T00039 are identified as different strains of Demequina lignilytica . Our study thus sheds light on the diversity, biological significance, and ecological contribution of the Demequina genus in different habitats.

Breaking the salty spell: Understanding action mechanism of melatonin and beneficial microbes as nature's solution for mitigating salt stress in soybean - Zhenyu Fan; Feifei He; Ting Wu; Bowen Li; Jin Xiao; Zhigang Wang (South African Journal of Botany, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Labdane and ent-halimane diterpenoids with STAT3-inhibitory activity from Leonurus sibiricus - Chen Wang; Jiao Tian; Chaoge Liu; Yiming He; Jiahang Li; Qiang Zhang; Ting Xiao; Chunfeng Xie; Cheng Yang (Phytochemistry, 2023)

Sperm quality decline associated with gaseous pollutant exposure: Evidence from a large cohort multicenter study - Xiaoyan Cai; Haobo Ni; Qiling Wang; Tingting Dai; Lingxi Wang; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Lina Xiao; Ting Xu; et al. (Journal of Hazardous Materials, 2023)

Efficient removal of Cr(VI) from wastewater by ZnO-polyacrylic acid/cellulose fiber/polyethylene glycol hydrogel: Synergistic effect of adsorption and photocatalytic reduction - Qing Li; Xiaojie Zhuang; Guanhong Zhou; Zhenfei Yang; Ting Yang; Hongbo Xiao; Tao Xu; Wenlei Wang (Journal of Environmental Chemical Engineering, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Effects of Fe and cost-effective media composition on arsenopyrite bioleaching by Sulfobacillus thermosulfidooxidans - Hong-Rui Chen; Duo-Rui Zhang; Xiao-Juan Zhao; Qian Li; Yu-Ting Liang; Eva Pakostova; Yan Zhang; Yong-Bin Yang (Chemical Engineering Journal, 2023)

Tree communities and functional traits determine herbivore compositional turnover - Ming-Qiang Wang; Zhixin Wen; Jinzhao Ke; Douglas Chesters; Yi Li; Jing-Ting Chen; Arong Luo; Xiaoyu Shi; Qing-Song Zhou; Xiao-Juan Liu; Keping Ma; Helge Bruelheide; et al. (Oecologia, 2023)

Imbalance of multiple neurotransmitter pathways leading to depression-like behavior and cognitive dysfunction in the triple transgenic mouse model of Alzheimer disease - Meng Zhang; Li-yuan Liu; Yong Xu; Wen-zhi Wang; Nian-zhuang Qiu; Fang-fang Zhang; Feng Zhang; Xiao-dan Wang; Wei Chen; Xiao-yan Xu; Yong-feng Gao; Mei-hua Chen; et al. (Metabolic Brain Disease, 2023)

Quantifying ant diversity and community in a subalpine forest mosaic: a comparison of two methods - Chuan-Jing Zhang; Yi-Ting Cheng; Xian-Shu Luo; Yao Chen; Yu-Chao He; Yan-Pang Li; Zhi-Pang Huang; Matthew B. Scott; Wen Xiao (Journal of Insect Conservation, 2023)
Sampling efficiency, composition and detection biases associated with pitfall-trap and sample plot (standardised hand-collecting) methods were compared at seven high montane sites at Lasha Mountain, Yunnan, China. Rarefaction-interpolation curves showed total species diversity and sample coverage from each method were undifferentiated. Permutational multivariate analysis of variance showed highly overlapping communities. However, of all species collected, just 53% of all species found were shared between the two methods; 30% were exclusive to sample plot samples and 17% were exclusive to pitfall traps. Modelled comparisons of species richness (alpha) and proportion of species from the population (beta diversity) showed differences between methods. Permutational multivariate analysis of variance blocked by site showed community composition differed between methods, defined largely by the presence of a few dominant species. Implications for insect conservation : Our findings suggest that results from the two methods cannot be directly compared and are imperfect substitutes to one another. For long-term monitoring of biodiversity in complex forest mosaic systems, we suggest integrating a suite of complementary methods to achieve more complete representation of ant composition and diversity.

A multi-sensor-based distributed real-time measurement system for glacier deformation - Han-chuan Dong; Shuang Liu; Li-li Pang; Zhi-gang Tao; Li-de Fang; Zhong-hua Zhang; Xiao-ting Li (Journal of Mountain Science, 2023)

4-vinylcyclohexene diepoxide induces apoptosis by excessive reactive oxygen species and DNA damage in human ovarian granulosa cells - Wei Song; Yu-Ting Qiu; Xiao-Zhen Li; Qing-Yuan Sun; Lei-Ning Chen (Toxicology in Vitro, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Petrography and geochemistry of the Permian-Triassic boundary interval, Kangjiaping section, South China: Implication for the drastic marine environment change - Xiao'er Zhu; Ting Liang; Zhenkui Jin; Shuo Yi; Yang Li; Hangshan Lei; Jiayu Li (Marine and Petroleum Geology, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

Overexpression of Taetr1-1 promotes enhanced seed dormancy and ethylene insensitivity in wheat - Jun Wei; Xing-ting Wu; Xiao-ying Li; Wim J. J. Soppe; Hong Cao; Yong-xiu Liu (Planta, 2023)

IRAK-M Ablation Promotes Status Epilepticus-Induced Neuroinflammation via Activating M1 Microglia and Impairing Excitatory Synaptic Function - Xiao-Shan Liang; Ting-Lin Qian; Yi-Fan Xiong; Xiao-Tao Liang; Yue-Wen Ding; Xiao-Yu Zhu; Yun-Lv Li; Jie-Li Zhou; Le-Yi Tan; Wei-Peng Li; Wei Xie (Molecular Neurobiology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Construction of PES mixed matrix membranes incorporating ZnFe2O4 @MXene composites with high permeability and antifouling performance - Ping Zhou; Ting Wang; Chun-Hui Du; Guo-qin Wang; Li-guang Wu; Xiao-jia Jiang; Hai-Chang Guo (Journal of Environmental Chemical Engineering, 2023)

High prevalence and genomic characteristics of carbapenem-resistant Enterobacteriaceae and colistin-resistant Enterobacteriaceae from large-scale rivers in China - Cai-Hong Guo; Yu-Qing Liu; Yan Li; Xiao-Xiao Duan; Ting-Yu Yang; Fang-Yu Li; Ming Zou; Bao-Tao Liu (Environmental Pollution, 2023)

A novel CD8+ T cell-related gene signature for predicting the prognosis and immunotherapy efficacy in bladder cancer - Fei Lin; Zhi-Bin Ke; Yu-Ting Xue; Jia-Yin Chen; Hai Cai; Yun-Zhi Lin; Xiao-Dong Li; Yong Wei; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

Correction: Changes in soil phosphorus fractions following the conversion of Chinese fir plantations to evergreen broad-leaved forests in subtropical China - Junjie Lei; Yuanying Peng; Juan Cao; Rujie Li; Qiang Jia; Xiao Shi; Ting Zhou; Wende Yan; Xiaoyong Chen (European Journal of Forest Research, 2023)

Changes in soil phosphorus fractions following the conversion of Chinese fir plantations to evergreen broad-leaved forests in subtropical China - Junjie Lei; Yuanying Peng; Juan Cao; Rujie Li; Qiang Jia; Xiao Shi; Ting Zhou; Wende Yan; Xiaoyong Chen (European Journal of Forest Research, 2023)

Quantification of radiation damage in natural and synthetic zircon by Raman spectroscopy: application to low-temperature thermochronology - Ke Su; Shao-Bing Zhang; John M. Hanchar; Zhen-Xin Li; Fang-Yuan Sun; Ting Liang; Xiao-Ying Gao (Acta Geochimica, 2023)

A systematic review: on the mercaptoacid metabolites of acrylamide, N-acetyl-S-(2-carbamoylethyl)-L-cysteine - Fang-Fang Zhao; Xiao-Li Wang; Ya-Ting Lei; Hong-Qiu Li; Zhi-Ming Li; Xiao-Xiao Hao; Wei-Wei Ma; Yong-Hui Wu; Sheng-Yuan Wang (Environmental Science and Pollution Research, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Microbial community composition and cooccurrence patterns driven by co-contamination of arsenic and antimony in antimony-mining area - Wei-song Pan; Qi Zou; Min Hu; Wai-chin Li; Xiao-ran Xiong; Yan-ting Qi; Chuan Wu (Journal of Hazardous Materials, 2023)

The bound polyphenols of foxtail millet (Setaria italica) inner shell inhibit breast cancer by promoting lipid accumulation-induced autophagic death - Li-chao Zhang; Ya-ning Liu; Xiao-qin La; Shuai-tao Li; Li-na Wen; Ting Liu; Han-qing Li; Ai-ping Li; Haitao Wu; Chang-xin Wu; Zhuo-yu Li (Food and Chemical Toxicology, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Insights into the Involvement and Therapeutic Target Potential of the Dopamine System in the Posttraumatic Stress Disorder - Meng-Nan Liu; Xiao-Yu Tian; Ting Fang; Ning Wu; Hong Li; Jin Li (Molecular Neurobiology, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

Will extreme temperature events emerge earlier under global warming? - Jinxing Sun; Ting Liu; Shuishi Xie; Juan Xiao; Li Huang; Zhiwei Wan; Keyuan Zhong (Atmospheric Research, 2023)

Analytical Solutions for the Characteristic Size Distribution of the Elliptical Model in Fractured Rock Mass - Kun Xiao; Ru Zhang; Jing Xie; Li Ren; Mingzhong Gao; Zetian Zhang; Chendi Lou; Ting Ai; Ersheng Zha (Rock Mechanics and Rock Engineering, 2023)

Soil organic matter content prediction using Vis-NIRS based on different wavelength optimization algorithms and inversion models - Wei Zhou; Jieyun Xiao; Haoran Li; Qi Chen; Ting Wang; Qian Wang; Tianxiang Yue (Journal of Soils and Sediments, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

Quick and high-throughput quantification of 22 β-agonists residues in animal-derived foods using enzymatic probe sonication - Zhiming Xiao; Jun Wang; Ying Cao; Ting Yao; Shi Wang; Jia Liu; Decheng Suo; Jing Tian; Zheng Jia; Yang Li; Xia Fan (Food Chemistry, 2023)

The importance of moisture in regulating soil organic carbon content based on a comparison of “enzymic latch” and “iron gate” in Zoige Plateau peatland - Ruixuan Li; Hanqing Luo; Jianlan Yu; Ling Luo; Yan He; Shihuai Deng; Ouping Deng; Dezhi Shi; Jinsong He; Hong Xiao; Lilin Wang; Ting Lan (CATENA, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Two new chemical constituents from the leaves of Illicium dunnianum - Jun-Ran Shao; Sen-Ju Ma; Ting Li; Xiao-Qing He; Zhen-Zhong Wang; Wei Xiao; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2023)

Extracting compositional blocks of alginate-like extracellular polymers (ALE) from conventional activated sludge (CAS) - Chen Shi; Run-Gen Zeng; Li-Ting Hao; Xiao-Di Hao; Ji Li (Science of The Total Environment, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Introduction of multilayered magnetic core–dual shell SERS tags into lateral flow immunoassay: A highly stable and sensitive method for the simultaneous detection of multiple veterinary drugs in complex samples - Jian Tu; Ting Wu; Qing Yu; Jiaxuan Li; Shuai Zheng; Kezong Qi; Guohui Sun; Rui Xiao; Chongwen Wang (Journal of Hazardous Materials, 2023)

Time-dependent effects of microplastics on soil bacteriome - Xuyuan Zhang; Yong Li; Junjie Lei; Ziqian Li; Qianlong Tan; Lingli Xie; Yunmu Xiao; Ting Liu; Xiaoyong Chen; Yafeng Wen; Wenhua Xiang; Yakov Kuzyakov; et al. (Journal of Hazardous Materials, 2023)

Insights into the pigment and non-pigment phenolic profile of polyphenol extracts of jujube peel and their antioxidant and lipid-lowering activities - Jin-Feng Dou; Cai-E Wu; Gong-Jian Fan; Ting-Ting Li; Xiao-Jing Li; Dan-Dan Zhou; Jin-Peng Zhu; Chun-Mei Li (Food Bioscience, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Comprehensive treatment strategy for diesel truck exhaust - Tian Li; Hai-Li Yang; Le-Tian Xu; Yu-Ting Zhou; Yong-Jun Min; Shi-Cheng Yan; Yong-Hui Zhang; Xiao-Ming Wang (Environmental Science and Pollution Research, 2023)

Potential antiplatelet aggregation metabolites from the discarded sorghum ( Sorghum bicolor L.) root - Wan-ting Xu; Qiao An; Ling-hui Ruan; Fei Zhou; Lang Zhou; Mei Peng; Li-lang Li; Xiao-sheng Yang; Qi-ji Li; Juan Yang (Natural Product Research, 2023)

Sonocatalytic degradation of tetracycline by BiOBr/FeWO4 nanomaterials and enhancement of sonocatalytic effect - Liang Xu; Xue-Qian Wu; Chun-Yu Li; Ni-Ping Liu; Hui-Li An; Wan-Ting Ju; Wen Lu; Bin Liu; Xiao-Fang Wang; Yang Wang; Xin Wang (Journal of Cleaner Production, 2023)

Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Nicosulfuron stress on the glyoxalase system and endogenous hormone content in sweet maize seedlings - Zhen-Xing Wu; Jian Wang; Xiao-Hu Lin; Qing Yang; Ting-Zhen Wang; Jian-Jian Chen; Xiang-Nan Li; Yuan Guan; Gui-Hua Lv (Environmental Science and Pollution Research, 2023)

Effect of chromium stress on metal accumulation and cell wall fractions in Cosmos bipinnatus - XiaoFang Yu; ZiHan Yang; YuHan Xu; ZhiWen Wang; ChunYu Fan; XiaoXuan Zeng; YuJia Liu; Ting Lei; MingYan Jiang; JiaNi Li; Xue Xiao; LiJuan Yang; et al. (Chemosphere, 2023)

Bioleaching and immobilizing of copper and zinc using endophytes coupled with biochar-hydroxyapatite: Bipolar remediation for heavy metals contaminated mining soils - Weiran Feng; Xiao Xiao; Junjie Li; Qicheng Xiao; Li Ma; Qifeng Gao; Yuke Wan; Yutian Huang; Ting Liu; Xubiao Luo; Shenglian Luo; Guisheng Zeng; et al. (Chemosphere, 2023)

The size of the susceptible pool differentiates climate effects on seasonal epidemics of bacillary dysentery - Haobo Ni; Qinghui Zeng; Ting Xu; Lina Xiao; Xiaolin Yu; Jinrui Hu; Yang Li; Hualiang Lin; Pi Guo; Haijian Zhou (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Anti-inflammatory diterpenoid alkaloids from Aconitum tanguticum (Maxim.) Stapf - Xiao Ye; Yue Wang; Qianwen Chen; Qingmei Feng; Ting Liu; Weihong Feng; Yaohua Liang; Xiaoqian Liu; Chun Li; Zhimin Wang (Phytochemistry, 2023)

Degradation mechanism and pathway of tetracycline in milk by heterojunction N-TiO2-Bi2WO6 film under visible light - Yuedeng Tang; Ting Li; Wenxuan Xiao; Zitong Huang; Huicui Wen; Wenbei Situ; Xianliang Song (Food Chemistry, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Micropyrones A and B, two new α -pyrones from the actinomycete Microbacterium sp. GJ312 isolated from Glycyrrhiza uralensis Fisch - Ying-Ting Xu; Yu-Cai Luo; Jing-Hua Xue; Yu-Ping Li; Lei Dong; Wen-Jun Li; Zhong-Yu Zhou; Xiao-Yi Wei (Natural Product Research, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Leading modes of wind field variability over the western Tibet Plateau - Jingzhi Wang; Xiao-Feng Li; Shaofeng Liu; Ting Liu; Yongjiu Dai; Song Yang; Hayley J. Fowler (Climate Dynamics, 2023)
Atmospheric circulations bring moisture from above the ocean to the high mountains of the western Tibet Plateau (TP), thus wind variability is of great importance to the water cycle centered on the western TP. This study therefore examines the leading modes of the wind fields over the western TP. We use the multivariate empirical orthogonal function (MV-EOF) analysis method to detect the dominant wind patterns above the western TP. This method extracts the leading modes of combined meridional and zonal wind variability at 200-hPa in the region of 22° N–50° N, 50° E–92° E. We find the first leading mode of the combined zonal and meridional wind field in the annual mean and in most seasons (spring, summer and autumn) over the western TP shows high similarity to the Western Tibetan Vortex (WTV), a large-scale atmospheric vortex-like pattern recently recognized over the western TP. In winter, the WTV, however, is closer to the second leading mode. We estimate the sensitivity of our results by changing the domain of the MV-EOF analysis region surrounding the western. We find the influence of the WTV is less sensitive to analysis location around the western TP. In short, the WTV generally represents the first leading mode of the wind field in most seasons over the western TP. This study augments our knowledge on wind variability over the western TP.

Nondestructive and rapid method for sex identification of the tropical sea cucumber Holothuria scabra by anal swab sampling - Zixuan E; Chuhang Cheng; Feifei Wu; Chunhua Ren; Rong Chen; Yingzhu Rao; Bo Ma; Xiao Jiang; Peng Luo; Xiaomin Li; Xin Zhang; Fajun Jiang; et al. (Aquaculture, 2023)

The toxic differentiation of micro- and nanoplastics verified by gene-edited fluorescent Caenorhabditis elegans - Wenxi Jiang; Wende Yan; Qianlong Tan; Yunmu Xiao; Yang Shi; Junjie Lei; Ziqian Li; Yuanyuan Hou; Ting Liu; Yong Li (Science of The Total Environment, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Transforming growth factor-β signaling: From tissue fibrosis to therapeutic opportunities - Li-Li Ren; Xiao-Jun Li; Ting-Ting Duan; Zheng-Hai Li; Jun-Zheng Yang; Ya-Mei Zhang; Liang Zou; Hua Miao; Ying-Yong Zhao (Chemico-Biological Interactions, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

Osteomodulin protects dental pulp stem cells from cisplatin-induced apoptosis in vitro - Ting Dong; Wen-zhen Lin; Xiao-han Zhu; Ke-yong Yuan; Li-li Hou; Zheng-wei Huang (Stem Cell Reviews and Reports, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

Immobilization of Cd2+ and Pb2+ by biomineralization of the carbonate mineralized bacterial consortium JZ1 - Peng Zhang; Xiao-Qiang Liu; Li-yuan Yang; Hua-ze-yu Sheng; An-qi Qian; Ting Fan (Environmental Science and Pollution Research, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

A Hashing-Based Framework for Enhancing Cluster Delineation of High-Dimensional Single-Cell Profiles - Xiao Liu; Ting Zhang; Ziyang Tan; Antony R. Warden; Shanhe Li; Edwin Cheung; Xianting Ding (Phenomics, 2022)

The enhanced removal of arsenite from water by double-shell CuOx@MnOy hollow spheres (DCMHS): behavior and mechanisms - Kun Wu; Birong Miao; Yuyang Xiao; Yang Li; Chuanqiao Zhang; Ting Liu; Shengjiong Yang; Jinfu Liu (Environmental Science and Pollution Research, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

A frequency ratio–based sampling strategy for landslide susceptibility assessment - Lei-Lei Liu; Yi-Li Zhang; Ting Xiao; Can Yang (Bulletin of Engineering Geology and the Environment, 2022)

Effects of U on the growth, reactive oxygen metabolism and osmotic regulation in radish (Raphanus sativus L.) - Guo Wu; Xi Chen; Ting Zheng; Pi-xian Xiao; Ning-ying Zhong; Xiu-lin Yang; Yi Li; Wei Li (Environmental Science and Pollution Research, 2022)

Dataset-based assessment of heavy metal contamination in freshwater fishes and their health risks - Xiao-Bo Liu; Congtian Lin; Yang-Yu Wu; Hai-Ning Huang; Li-Ting Zhu; Ru Jiang; Qiansheng Huang (Environmental Science and Pollution Research, 2022)

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Efficient seismic data reconstruction based on Geman function minimization - Yan-Yan Li; Li-Hua Fu; Wen-Ting Cheng; Xiao Niu; Wan-Juan Zhang (Applied Geophysics, 2022)

The relative importance of intraspecific variation in above- and belowground plant traits in shaping salt marsh soil bacterial diversity and composition - Hao Liu; Ting Zhu; Xiao Xu; Jia Yao; Chenhao Zhou; Jihua Wu; Bo Li; Ming Nie (Plant and Soil, 2022)

Distinct co-occurrence patterns and driving forces of abundant and rare bacterial communities in the multispecies solid-state fermentation process of cereal vinegar - Ming-Ye Peng; Zhen-Ming Lu; Xiao-Juan Zhang; Ting Huang; Yong-Jian Deng; Li-Juan Chai; Jin-Song Shi; Zheng-Hong Xu (Systems Microbiology and Biomanufacturing, 2022)

Crocin Alleviates Intracerebral Hemorrhage–Induced Neuronal Ferroptosis by Facilitating Nrf2 Nuclear Translocation - Fei Wang; Wu-lin Li; Li-juan Shen; Ting-ting Jiang; Jian-jun Xia; Da-li You; Shan-you Hu; Li Wang; Xiao Wu (Neurotoxicity Research, 2022)

Baicalin attenuates amyloid β oligomers induced memory deficits and mitochondria fragmentation through regulation of PDE-PKA-Drp1 signalling - Hai-Yang Yu; Ye Zhu; Xin-Li Zhang; Lei Wang; Yan-Meng Zhou; Fang-Fang Zhang; Han-Ting Zhang; Xiao-Min Zhao (Psychopharmacology, 2022)

A Facile Probe for Fluorescence Turn-on and Simultaneous Naked-Eyes Discrimination of H2S and biothiols (Cys and GSH) and Its Application - Ting-Ting Liu; Shi-Jie Li; Xiao-Song Zhang; Jing Wang; Yun-Xiu Deng; Xue-Jiao Sun; Zhi-Yong Xing; Ruo-Fei Wu (Journal of Fluorescence, 2022)

Dynamic analysis of impulse waves generated by the collapse of granular pillars - Bo-lin Huang; Bin Li; Jia-hao Zheng; Wang-li Feng; Xiao-ting Chen; Chao-lin Luo (Journal of Mountain Science, 2022)

Hydrogen Sulfide Maintains Good Nutrition and Delays Postharvest Senescence in Postharvest Tomato Fruits by Regulating Antioxidative Metabolism - Ting-Ying Zhong; Gai-Fang Yao; Sha-Sha Wang; Ting-Ting Li; Ke-Ke Sun; Jun Tang; Zhong-Qin Huang; Feng Yang; Yan-Hong Li; Xiao-Yan Chen; Lan-Ying Hu; Hua Zhang; et al. (Journal of Plant Growth Regulation, 2021)

Clinical and Molecular Features of POLG-Related Sensory Ataxic Neuropathy with Dysarthria and Ophthalmoparesis - Li-Xi Li; Li-Ting Jiang; You-Gui Pan; Xiao-Long Zhang; Li-Zhen Pan; Zhi-Yu Nie; Yu-Hui Chen; Ling-Jing Jin (Journal of Molecular Neuroscience, 2021)

Three new diterpenoids from Euphorbia peplus - Yan-Ni Chen; Qing-Yun Lu; Dong-Mei Li; Ying-Yao Li; Xue-Xue Pu; Bo-Ting Li; Xiao-Han Tang; Hong-Yu Tang; Shuai Liu; Lei Yang; Yu Zhang; Ying-Tong Di; et al. (Natural Product Research, 2021)

Reduced acetylcholine and elevated muscarinic receptor 2 in duodenal mucosa contribute to the impairment of mucus secretion in 6-hydroxydopamine-induced Parkinson’s disease rats - Jing-Ting Yan; Xiao-Yu Liu; Jing-Hua Liu; Guang-Wen Li; Li-Fei Zheng; Xiao-Li Zhang; Yue Zhang; Xiao-Yan Feng; Jin-Xia Zhu (Cell and Tissue Research, 2021)

Pseudotime Ordering Single-Cell Transcriptomic of β Cells Pancreatic Islets in Health and Type 2 Diabetes - Kaixuan Bao; Zhicheng Cui; Hui Wang; Hui Xiao; Ting Li; Xingxing Kong; Tiemin Liu (Phenomics, 2021)

Structure–activity relationship studies on Pd176252 derivatives leading to discovery of novel GRP receptor antagonist with potent anticancer activity - Ming-jun Yu; Chao Li; Meng He; Yu-ting Zhu; Rui Yang; Sheng-song Deng; Xiao-ming Meng; Ri-sheng Yao (Medicinal Chemistry Research, 2021)

Petrogenesis of the early Permian A-type granites in the Halajun region, southwest Tianshan, western Xinjiang, NW China: implications for geodynamics of Tarim large igneous province - Zhao-Jian Zong; Yang-Song Du; Shun-Ting Li; Yi Cao; Jing-Guo Du; Xiao-Hua Deng; Li-Wei Xue (International Geology Review, 2021)

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

The hand-arm vibration syndrome associated with the grinding of handheld workpieces in a subtropical environment - Nuoyan Wei; Hansheng Lin; Ting Chen; Bin Xiao; Maosheng Yan; Li Lang; Hongyu Yang; Shan Wu; Paul-Émile Boileau; Qingsong Chen (International Archives of Occupational and Environmental Health, 2021)

Calcium signalling mediated the regulation of growth and polysaccharide accumulation by light quality in Dendrobium officinale protocorms - Ting Lei; Suping Gao; Xiao Lin; Kaihui Zhang; Yingqi Liu; Wenji Li; Di Hu; Xiaofang Yu; Mingyan Jiang; Qibing Chen; Ying Sun (Horticulture, Environment, and Biotechnology, 2021)

Mass spectrometry-based proteomic analysis of potential infectious bursal disease virus VP3-interacting proteins in chicken embryo fibroblasts cells - Sun-Ting Ma; Yong-Shan Wang; Xiao-Li Wang; Xing-Xia Xia; Zhen-Wei Bi; Jing-Yu Wang; Yu-Mei Zhu; Wei Ouyang; Jing Qian (Virus Genes, 2021)

CYT387, a Novel JAK2 Inhibitor, Suppresses IL-13-Induced Epidermal Barrier Dysfunction Via miR-143 Targeting IL-13Rα1 and STAT3 - Yan Zu; Xiao-Fei Chen; Qiang Li; Shu-Ting Zhang (Biochemical Genetics, 2021)

EmhR is an indole‐sensing transcriptional regulator responsible for the indole‐induced antibiotic tolerance in Pseudomonas fluorescens - Jian‐Ting Han; Di‐Yin Li; Meng‐Yuan Zhang; Xiao‐Quan Yu; Xiang‐Xue Jia; Hang Xu; Xu Yan; Wen‐Juan Jia; Shaomin Niu; Megan L. Kempher; Xuanyu Tao; Yong‐Xing He (Environmental Microbiology, 2021)
Summary Indole is well known as an interspecies signalling molecule to modulate bacterial physiology; however, it is not clear how the indole signal is perceived and responded to by plant growth promoting rhizobacteria (PGPR) in the rhizosphere. Here, we demonstrated that indole enhanced the antibiotic tolerance of Pseudomonas fluorescens 2P24, a PGPR well known for its biocontrol capacity. Proteomic analysis revealed that indole influenced the expression of multiple genes including the emhABC operon encoding a major multidrug efflux pump. The expression of emhABC was regulated by a TetR‐family transcription factor EmhR, which was demonstrated to be an indole‐responsive regulator. Molecular dynamics simulation showed that indole allosterically affected the distance between the two DNA‐recognizing helices within the EmhR dimer, leading to diminished EmhR–DNA interaction. It was further revealed the EmhR ortholog in Pseudomonas syringae was also responsible for indole‐induced antibiotic tolerance, suggesting this EmhR‐dependent, indole‐induced antibiotic tolerance is likely to be conserved among Pseudomonas species. Taken together, our results elucidated the molecular mechanism of indole‐induced antibiotic tolerance in Pseudomonas species and had important implications on how rhizobacteria sense and respond to indole in the rhizosphere.

Thiazole-based and thiazolidine-based protein tyrosine phosphatase 1B inhibitors as potential anti-diabetes agents - Kexin Chen; Xu Yao; Ting Tang; Li-Mei Chen; Can Xiao; Jing-Yi Wang; Hong-Fei Chen; Zhong-Xing Jiang; Yi Liu; Xing Zheng (Medicinal Chemistry Research, 2021)

Macrolactins: biological activity and biosynthesis - Ting Wu; Fei Xiao; Wenli Li (Marine Life Science & Technology, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Transcription factor MoMsn2 targets the putative 3‐methylglutaconyl‐CoA hydratase‐encoding gene MoAUH1 to govern infectious growth via mitochondrial fusion/fission balance in Magnaporthe oryzae - Yuhan Xiao; Luping Liu; Ting Zhang; Ruiwen Zhou; Yuan Ren; Xinrui Li; Haidong Shu; Wenwu Ye; Xiaobo Zheng; Zhengguang Zhang; Haifeng Zhang (Environmental Microbiology, 2021)
Summary Mitochondrial quality and quantity are essential for a cell to maintain normal cellular functions. Our previous study revealed that the transcription factor MoMsn2 plays important roles in the development and virulence of Magnaporthe oryzae . However, to date, no study has reported its underlying regulatory mechanism in phytopathogens. Here, we explored the downstream target genes of MoMsn2 using a chromatin immunoprecipitation sequencing (ChIP‐Seq) approach. In total, 332 target genes and five putative MoMsn2‐binding sites were identified. The 332 genes exhibited a diverse array of functions and the highly represented were genes involved in metabolic and catalytic processes. Based on the ChIP‐Seq data, we found that MoMsn2 plays a role in maintaining mitochondrial morphology, likely by targeting a number of mitochondria‐related genes. Further investigation revealed that MoMsn2 targets the putative 3‐methylglutaconyl‐CoA hydratase‐encoding gene ( MoAUH1 ) to control mitochondrial morphology and mitophagy, which are critical for the infectious growth of the pathogen. Meanwhile, the deletion of MoAUH1 resulted in phenotypes similar to the Δ Momsn2 mutant in mitochondrial morphology, mitophagy and virulence. Overall, our results provide evidence for the regulatory mechanisms of MoMsn2, which targets MoAUH1 to modulate its transcript levels, thereby disturbing the mitochondrial fusion/fission balance. This ultimately affects the development and virulence of M . oryzae .

Hypoxia/reoxygenation-induced upregulation of miRNA-542-5p aggravated cardiomyocyte injury by repressing autophagy - Fei Wang; Xin Min; Shan-you Hu; Da-li You; Ting-ting Jiang; Li Wang; Xiao Wu (Human Cell, 2021)

Intramuscular injection of tetracycline decreased gut microbial diversity in mouse - Jia Liu; Xi-chuan Deng; Xiao-yu Li; Zhi-bang Yang; Guang-yuan Zhang; Ting-ting Chen (Mammalian Genome, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Transcriptome analysis of rice leaves in response to Rhizoctonia solani infection and reveals a novel regulatory mechanism - De Peng Yuan; Xiao Feng Xu; Woo-Jong Hong; Si Ting Wang; Xin Tong Jia; Yang Liu; Shuang Li; Zhi Min Li; Qian Sun; Qiong Mei; Shuai Li; Ki-Hong Jung; et al. (Plant Biotechnology Reports, 2020)

2(5H)-Furanone Disrupts Bacterial Biofilm Formation and Indirectly Reduces the Settlement of Plantigrades of the Mussel Mytilus coruscus - Yi-Feng Li; Xin Zhu; Zhi-Yang Cheng; Xiao Liang; You-Ting Zhu; Dan-Dan Feng; Sergey Dobretsov; Jin-Long Yang (Frontiers in Marine Science, 2020)

Chemical composition of Erycibe schmidtii and antiproliferative activity of scopoletin on immature dendritic cells - Wang Ren; Yantang Wang; Qinhui He; Yue Zhou; Chunxin Li; Wenling Wang; Xiao Leng; Ting Zeng; Qiang Zou; Limei Li (Natural Product Research, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

Chopper Sugarcane Combine Harvester with Middle-Mounted Primary Extractor - Tao Wu; Xiao-Ling Liang; Qing-Ting Liu; Zeng-Xue Zhang; Hai Xu; Ji-Bai Huang; Jin-Xin Li; Xiao-Ping Zou (Sugar Tech, 2020)

Alfalfa MsCBL4 enhances calcium metabolism but not sodium transport in transgenic tobacco under salt and saline–alkali stress - Yimin An; Xiao-Xue Yang; Lishuang Zhang; Jun Zhang; Binghao Du; Lin Yao; Xiu-ting Li; Changhong Guo (Plant Cell Reports, 2020)

Transcriptome Analysis of Two Strains of Proteus mirabilis with Swarming Migration Deficiency Isolated from Patients with Urinary Tract Infection - Liang Peng; Ding-Qiang Chen; Guan-Ming Jiang; Jing-Yi Ou; Qiao Jiang; Li-Ting Zeng; Yi Xiao; Qiong-Yan Jiang; Ling Yang; Ning Sun (Current Microbiology, 2020)

Acanthophoraine A, a new pyrrolidine alkaloid from the red alga Acanthophora spicifera - Jia-Li Lin; Yong-Qian Liang; Xiao-Jian Liao; Jian-Ting Yang; Dai-Chun Li; Yu-Ling Huang; Zhi-Hui Jiang; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2020)

Ocean surface current retrieval at Hangzhou Bay from Himawari-8 sequential satellite images - Zhenye Zhu; Xupu Geng; Shihui Li; Ting Xie; Xiao-Hai Yan (Science China Earth Sciences, 2020)

Nitric Oxide Negatively Regulates Larval Metamorphosis in Hard-Shelled Mussel (Mytilus coruscus) - You-Ting Zhu; Ya Zhang; Yu-Zhu Liu; Yi-Feng Li; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang; Xiao Liang (Frontiers in Marine Science, 2020)

Antifungal, anti-inflamatory and neuritogenic activity of newly-isolated compounds from Disporopsis aspersa - Fang-Li Gang; Feng Zhu; Chao-Fu Yang; Xiao-Ting Li; Hua Yang; Ming-Xia Sun; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Expression Patterns of Inducible Cre Recombinase Driven by Differential Astrocyte-Specific Promoters in Transgenic Mouse Lines - Neng-Yuan Hu; Ya-Ting Chen; Qian Wang; Wei Jie; Yi-Si Liu; Qiang-Long You; Ze-Lin Li; Xiao-Wen Li; Sophie Reibel; Frank W. Pfrieger; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

The Arabidopsis UDP-glycosyltransferase75B1, conjugates abscisic acid and affects plant response to abiotic stresses - Ting-Ting Chen; Fang-Fei Liu; Dong-Wang Xiao; Xiao-Yi Jiang; Pan Li; Shu-Man Zhao; Bing-kai Hou; Yan-jie Li (Plant Molecular Biology, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

A blessing for the Yangtze River: optimization of Chinese regional policy planning for water yield and purification in the Three Gorges Reservoir Area - Qinli Xiong; Yang Xiao; Marwa Waseem A. Halmy; Kaiwen Pan; Mohammed A. Dakhil; Lin Zhang; Ting Li; Pinghan Liang (Environmental Science and Pollution Research, 2020)

Fine Mapping of the High-pH Tolerance and Growth Trait-Related Quantitative Trait Loci (QTLs) and Identification of the Candidate Genes in Pacific White Shrimp (Litopenaeus vannamei) - Wen Huang; Chuhang Cheng; Jinshang Liu; Xin Zhang; Chunhua Ren; Xiao Jiang; Ting Chen; Kaimin Cheng; Huo Li; Chaoqun Hu (Marine Biotechnology, 2020)

Adjuvant therapy with Astragalus membranaceus for post-stroke fatigue: a systematic review - Li Xu; Xiao-Yan Xu; Xue-Qin Hou; Fu-Gang Wang; Shan Gao; Han-Ting Zhang (Metabolic Brain Disease, 2020)

Metabolomics and physiological analyses reveal β-sitosterol as an important plant growth regulator inducing tolerance to water stress in white clover - Zhou Li; Bizhen Cheng; Bin Yong; Ting Liu; Yan Peng; Xinquan Zhang; Xiao Ma; Linkai Huang; Wei Liu; Gang Nie (Planta, 2019)

Genomic characterization of a novel astrovirus identified in Amur tigers from a zoo in China - Hui-Hui Zhang; Qi-Guan Qiu; Shu-Jing Liu; Wen-Qin Hu; Jie-Yu Li; Tian-Ning Liu; You-Song Peng; Xing-Yi Ge; Chao-Ting Xiao (Archives of Virology, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

High genetic diversity and recombination events of porcine astrovirus strains identified from ill and asymptomatic pigs in 2017, Hunan Province, China - Sun-Liang Lv; Hui-Hui Zhang; Jie-Yu Li; Wen-Qin Hu; Ya-Ting Song; Tanja Opriessnig; Chao-Ting Xiao (Virus Genes, 2019)

Fusarium oxysporum KB-3 from Bletilla striata: an orchid mycorrhizal fungus - Jianwei Jiang; Ke Zhang; Sheng Cheng; Qianwen Nie; Shen-xian Zhou; Qingqing Chen; Jinglong Zhou; Xiao Zhen; Xue ting Li; Tong wen Zhen; Mingyue Xu; Tom Hsiang; et al. (Mycorrhiza, 2019)

Cholesterol transport through the peroxisome-ER membrane contacts tethered by PI(4,5)P2 and extended synaptotagmins - Jian Xiao; Jie Luo; Ao Hu; Ting Xiao; Meixin Li; Zekai Kong; Luyi Jiang; Zimu Zhou; Yacheng Liao; Chang Xie; Beibei Chu; Honghua Miao; et al. (Science China Life Sciences, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

Emission of nitrous oxide from plain multi-ditch system and its impact factors - Ouping Deng; Xi Li; Yinlong Xiao; Shirong Zhang; Liangji Deng; Ting Lan; Ling Luo; Xuesong Gao; Wei Zhou; Jing Zhang; Jing Ling (Environmental Science and Pollution Research, 2019)

Design and Experiment of Clamper Used in Antarctic Subglacial Bedrock Drilling - Pavel Talalay; Xingchen Li; Da Gong; Xiaopeng Fan; Nan Zhang; Yang Yang; Yongwen Liu; Yunchen Liu; Ting Wang; Xiao Li (Journal of Marine Science and Engineering, 2019)
As a result of the severe natural environment with oxygen deficit in the Antarctic, using conventional manual work to screw and unscrew the drill pipe increases the labor intensity tremendously and causes an efficiency reduction. Therefore, it would be useful to design a clamper inside the drilling shelter, which could help to assemble and disassemble the ice core barrel with screw connection. This paper describes the design of and experiments with the clamper inside the movable drilling shelter. A related testing stand was also designed and built to experiment on relationships between the clamper motor current versus clamping torque and force. Through experimental data collation and calculation analysis, the following conclusions could be drawn: (1) according to the rotary ability of the Ice and Bedrock Electromechanical Drill (IBED) to calculate and determine the torque of clamper, the clamping torque required to provide by the clamper is 100 N·m; (2) finite element simulation and analysis of the non-standard transmission chain showed that the mechanical reliability of the subparts; (3) the experimental results showed the range of the clamping force and clamping torque of the clamper. The clamping force and clamping torque increased with the increase of clamper DC motor current, presenting proportional linear relationships. The clamper can meet the clamping requirements of IBED for screwing, unscrewing, and clamping, which will be greatly helpful when it is tested in the field.

Evaluation of laboratory diagnostic approaches for tuberculous pleurisy - Xiao-Chun Shi; Yu-Ting Tan; Li-Fan Zhang; Yue-Qiu Zhang; Xiao-Qing Liu (Infectious Diseases, 2019)

Dynamic monitoring of resuspension in the multiple eco-types of the littoral zone of a shallow wind-disturbed lake - Chuang Qi; Yang Zhou; Xiao-guang Xu; Li-min Zhang; Hui Lin; Xin-ting Wu; Kuan Shi; Guo-xiang Wang (Aquatic Sciences, 2019)

Identification of key genes relevant to the prognosis of ER-positive and ER-negative breast cancer based on a prognostic prediction system - Bin Xiao; Jianfeng Hang; Ting Lei; Yongyin He; Zhenzhan Kuang; Li Wang; Lidan Chen; Jia He; Weiyun Zhang; Yang Liao; Zhaohui Sun; Linhai Li (Molecular Biology Reports, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Geochemistry, zircon U–Pb geochronology and Hf isotopes of Jurassic-Cretaceous granites in the Tengchong terrane, SW China: implications for the Mesozoic tectono-magmatic evolution of the Eastern Tethyan Tectonic Domain - Hua-Wen Cao; Yun-Hui Zhang; Li Tang; Steven P. Hollis; Shou-Ting Zhang; Qiu-Ming Pei; Chang Yang; Xiao-Shuan Zhu (International Geology Review, 2019)

Contribution of Cathepsin L to Autolysis of Sea Cucumber Stichopus japonicus Intestines - Jia-Nan Yan; Xiao-Kun Guo; Yue Tang; Ao-Ting Li; Zhi-Mo Zhu; Xiao-Qian Chai; Xiu-Hong Duan; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2019)

Two new polyketides from the fungus Penicillium oxalicum MHZ153 - Yi Ren; Ling-Hui Chao; Jing Sun; Xiao-Nan Chen; Hui-Na Yao; Zhi-Xiang Zhu; Dan Dong; Ting Liu; Peng-Fei Tu; Jun Li (Natural Product Research, 2019)

Theoretical study of the mechanism of the manganese catalase KatB - Xi-Xi Yang; Qiu-Yun Mao; Xiao-Ting An; Xi-Chen Li; Per E. M. Siegbahn; Guang-Ju Chen; Hong-Wei Tan (JBIC Journal of Biological Inorganic Chemistry, 2019)

Adsorption characteristics of Cu(II) and Zn(II) by nano-alumina material synthesized by the sol-gel method in batch mode - Ren-yu Wang; Wei Zhang; Li-ying Zhang; Tian Hua; Gang Tang; Xiao-qian Peng; Ming-hui Hao; Qi-ting Zuo (Environmental Science and Pollution Research, 2019)

Transcriptome-Based Identification of a Strong Promoter for Hyper-production of Natamycin in Streptomyces - Kai Wang; Xiao-Fang Liu; Qing-Ting Bu; Yang Zheng; Xin-Ai Chen; Yong-Quan Li; Xu-Ming Mao (Current Microbiology, 2019)

Rapid Screening of Maize Inbred Lines Based on NIR-MIR Spectral Characteristics and Small-molecule Metabolites - Meng Ting Li; Ren Jie Yang; Hai Xue Liu; Yang Liu; Xiao Qian Zhang; Xiao Dong Xie (Journal of Crop Science and Biotechnology, 2018)

Augmenter of liver regeneration promotes mitochondrial biogenesis in renal ischemia–reperfusion injury - Li-li Huang; Rui-ting Long; Gui-ping Jiang; Xiao Jiang; Hang Sun; Hui Guo; Xiao-hui Liao (Apoptosis, 2018)

Two new alkylated furan derivatives with antifungal and antibacterial activities from the plant endophytic fungus Emericella sp. XL029 - Xia Wu; Xue-Jiao Pang; Lu-Lin Xu; Ting Zhao; Xin-Yu Long; Qiong-Yin Zhang; Hai-Li Qin; Deng-Feng Yang; Xiao-Long Yang (Natural Product Research, 2018)

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor of 30-Day Mortality of Intracerebral Hemorrhage Patients: a Validation Cohort Study - Fei Wang; Li Wang; Ting-ting Jiang; Jian-jun Xia; Feng Xu; Li-juan Shen; Wen-hui Kang; Yong Ding; Li-xia Mei; Xue-feng Ju; Shan-you Hu; Xiao Wu (Neurotoxicity Research, 2018)

Luteolin alleviates cardiac ischemia/reperfusion injury in the hypercholesterolemic rat via activating Akt/Nrf2 signaling - Jin-Ting Yang; Jue Wang; Xin-Ru Zhou; Chi Xiao; Yang-Yun Lou; Li-Hui Tang; Feng-Jiang Zhang; Ling-Bo Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

A comparison of CRISPR/Cas9 and siRNA-mediated ALDH2 gene silencing in human cell lines - Fei Wang; Tao Guo; Hongmei Jiang; Ruobi Li; Ting Wang; Ni Zeng; Guanghui Dong; Xiaowen Zeng; Daochuan Li; Yongmei Xiao; Qiansheng Hu; Wen Chen; et al. (Molecular Genetics and Genomics, 2018)

Variation in accumulation, transport, and distribution of phthalic acid esters (PAEs) in soil columns grown with low- and high-PAE accumulating rice cultivars - Yang Wu; Xue-Xue Chen; Ting-Kai Zhu; Xing Li; Xiao-Hong Chen; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

OsPKS2 is required for rice male fertility by participating in pollen wall formation - Ting Zou; Mingxing Liu; Qiao Xiao; Tao Wang; Dan Chen; Tao Luo; Guoqiang Yuan; Qiao Li; Jun Zhu; Yueyang Liang; Qiming Deng; Shiquan Wang; et al. (Plant Cell Reports, 2018)

Intrinsic renal cells induce lymphocytosis of Th22 cells from IgA nephropathy patients through B7–CTLA-4 and CCL-CCR pathways - Lu Gan; Qiaoling Zhou; Xiaozhao Li; Chen Chen; Ting Meng; Jiaxi Pu; Mengyuan Zhu; Chenggen Xiao (Molecular and Cellular Biochemistry, 2018)

Isolation and identification of bovine nasopharyngeal mucosal epithelial cells and establishment of cell models of acute infection by foot-and-mouth disease virus - Wan-fu Bai; Lu Li; Ting Zhang; Xiao-hu Su; Yong-wei Wang; Bing-wu Zhao; Tao Zhang; Huan-min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2018)

Predictive modeling of microbial single cells: A review - Tian Ding; Xin-Yu Liao; Qing-Li Dong; Xiao-Ting Xuan; Shi-Guo Chen; Xing-Qian Ye; Dong-Hong Liu (Critical Reviews in Food Science and Nutrition, 2018)

Exclosure on CT-measured soil macropore characteristics in the Inner Mongolia grassland of northern China - Xia Hu; Yan-Li Lyu; Yong Liu; Xiao-Yan Li; Zhen-Ting Sun; Zong-Chao Li; Ya-Qian Cheng; Lan-Lan Guo; Lian-You Liu (Journal of Soils and Sediments, 2018)

Combined effects of aspirin and vitamin D3 on two OSCC cell lines: a preliminary study - Ting-Ting Xiao; Xian Li; Jia-Li Feng; Yong Li (Biotechnology Letters, 2018)

Compounds with inhibitory activity on peristalsis from the seeds of Holarrhena antidysenterica - Hai-Hua Xie; Jian Su; Xiao-Lei Ge; Ting-Ting Dong; Xin Li; Hui-Min Wen; Bo-Hang Sun (Natural Product Research, 2018)

Effect of hydrogen-rich water on vase life and quality in cut lily and rose flowers - Peng-Ju Ren; Xin Jin; Wei-Biao Liao; Meng Wang; Li-Juan Niu; Xue-Ping Li; Xiao-Ting Xu; Yong-Chao Zhu (Horticulture, Environment, and Biotechnology, 2017)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

Serum Copeptin Predicts Severity and Recurrent Stroke in Ischemic Stroke Patients - Wan-Zhong Tang; Xiao-Bo Wang; Huan-Ting Li; Mei Dong; Xiang Ji (Neurotoxicity Research, 2017)

The phosphodiesterase-4 inhibitor roflumilast decreases ethanol consumption in C57BL/6J mice - Xin Liu; Pi-Da Hao; Ming-Feng Yang; Jing-Yi Sun; Lei-Lei Mao; Cun-Dong Fan; Zong-Yong Zhang; Da-Wei Li; Xiao-Yi Yang; Bao-Liang Sun; Han-Ting Zhang (Psychopharmacology, 2017)

Orexin Directly Enhances the Excitability of Globus Pallidus Internus Neurons in Rat by Co-activating OX1 and OX2 Receptors - He-Ren Gao; Qian-Xing Zhuang; Yong-Xiao Zhang; Zhang-Peng Chen; Bin Li; Xiao-Yang Zhang; Yi-Ting Zhong; Jian-Jun Wang; Jing-Ning Zhu (Neuroscience Bulletin, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Protective effects of vitamins C and E on dichlorodiphenyltrichloroethane-induced genotoxicity and hepatotoxicity in human liver cells - Xiao Ting Jin; Li Song; Xiang Yuan Liu; Hang Qing Li; Long Cheng; Zhuo Yu Li (Molecular & Cellular Toxicology, 2017)

Verticillium dahliae manipulates plant immunity by glycoside hydrolase 12 proteins in conjunction with carbohydrate‐binding module 1 - Yue‐Jing Gui; Jie‐Yin Chen; Dan‐Dan Zhang; Nan‐Yang Li; Ting‐Gang Li; Wen‐Qi Zhang; Xin‐Yan Wang; Dylan P. G. Short; Lei Li; Wei Guo; Zhi‐Qiang Kong; Yu‐Ming Bao; et al. (Environmental Microbiology, 2017)
Summary Glycoside hydrolase 12 (GH12) proteins act as virulence factors and pathogen‐associated molecular patterns (PAMPs) in oomycetes. However, the pathogenic mechanisms of fungal GH12 proteins have not been characterized. In this study, we demonstrated that two of the six GH12 proteins produced by the fungus Verticillium dahliae Vd991, VdEG1 and VdEG3 acted as PAMPs to trigger cell death and PAMP‐triggered immunity (PTI) independent of their enzymatic activity in Nicotiana benthamiana . A 63‐amino‐acid peptide of VdEG3 was sufficient for cell death‐inducing activity, but this was not the case for the corresponding peptide of VdEG1. Further study indicated that VdEG1 and VdEG3 trigger PTI in different ways: BAK1 is required for VdEG1‐ and VdEG3‐triggered immunity, while SOBIR1 is specifically required for VdEG1‐triggered immunity in N. benthamiana . Unlike oomycetes, which employ RXLR effectors to suppress host immunity, a carbohydrate‐binding module family 1 (CBM1) protein domain suppressed GH12 protein‐induced cell death. Furthermore, during infection of N. benthamiana and cotton, VdEG1 and VdEG3 acted as PAMPs and virulence factors, respectively indicative of host‐dependent molecular functions. These results suggest that VdEG1 and VdEG3 associate differently with BAK1 and SOBIR1 receptor‐like kinases to trigger immunity in N. benthamiana , and together with CBM1‐containing proteins manipulate plant immunity.

Plastomes of Mimosoideae: structural and size variation, sequence divergence, and phylogenetic implication - Yin-Huan Wang; Xiao-Jian Qu; Si-Yun Chen; De-Zhu Li; Ting-Shuang Yi (Tree Genetics & Genomes, 2017)

Serum Resistin Levels May Contribute to an Increased Risk of Acute Cerebral Infarction - Xiao-Liu Dong; Shi-Jun Xu; Li Zhang; Xiu-Qing Zhang; Ting Liu; Qiu-Yan Gao; Qing-Qiang Qian; Bao-Liang Sun; Ming-Feng Yang (Molecular Neurobiology, 2017)

Identification and characterization of multiple porcine astrovirus genotypes in Hunan province, China - Chao-Ting Xiao; Zhang Luo; Sun-Liang Lv; Tanja Opriessnig; Run-Cheng Li; Xing-Long Yu (Archives of Virology, 2017)

Nr3C1-Bhlhb2 Axis Dysregulation Is Involved in the Development of Attention Deficit Hyperactivity - Li Hui Wu; Wei Cheng; Mei Yu; Bao Mei He; Hui Sun; Qi Chen; Yi Wei Dong; Xiao Ting Shao; Qian Qian Cai; Min Peng; Xing Zhong Wu (Molecular Neurobiology, 2017)

Vimentin is important in the neural differentiation of PC12 cells promoted by sialylation - Li Hui Wu; Xiao Ting Shao; Jun Xia Guo; Hui Sun; Qi Chen; Jing Pan; Qian Qian Cai; Yi Wei Dong; Zhong Yi Chen; Xiao Mei Yan; Min Peng; Nanbert Zhong; et al. (Glycoconjugate Journal, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Purified isolation of vacuoles from Sedum alfredii leaf-derived protoplasts - Xiao-yu Gao; Xing-cheng Liao; Ruo-lai Wu; Ting Liu; Hai-xing Wang; Ling-li Lu (Journal of Zhejiang University-SCIENCE B, 2017)

A new armored archosauriform (Diapsida: Archosauromorpha) from the marine Middle Triassic of China, with implications for the diverse life styles of archosauriforms prior to the diversification of Archosauria - Chun Li; Xiao-chun Wu; Li-jun Zhao; Sterling J. Nesbitt; Michelle R. Stocker; Li-Ting Wang (The Science of Nature, 2016)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Hydrogen peroxide is involved in abscisic acid-induced adventitious rooting in cucumber (Cucumis sativus L.) under drought stress - Xue-Ping Li; Qing-Qing Xu; Wei-Biao Liao; Zhan-Jun Ma; Xiao-Ting Xu; Meng Wang; Peng-Ju Ren; Li-Juan Niu; Xin Jin; Yong-Chao Zhu (Journal of Plant Biology, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Progression and inflammation of human myeloid leukemia induced by ambient PM2.5 exposure - Xiao-Ting Jin; Mei-Lan Chen; Rui-Jin Li; Quan An; Li Song; Yi Zhao; Hong Xiao; Long Cheng; Zhuo-Yu Li (Archives of Toxicology, 2016)

Effect of Dynamic Culture and Periodic Compression on Human Mesenchymal Stem Cell Proliferation and Chondrogenesis - Ting Guo; Li Yu; Casey G. Lim; Addison S. Goodley; Xuan Xiao; Jesse K. Placone; Kimberly M. Ferlin; Bao-Ngoc B. Nguyen; Adam H. Hsieh; John P. Fisher (Annals of Biomedical Engineering, 2016)

Cloning, molecular characterization, and expression analysis of the unc45 myosin chaperone b(unc45b)gene of grass carp (Ctenopharyngodon idellus) - Jing Hu; Ting Guo; Wen-Qian Pan; Tian Gan; Jing Wei; Jun-Peng Wang; Xiang-Jun Leng; Xiao-Qin Li (Journal of Muscle Research and Cell Motility, 2016)

Cytotoxic monoterpenoid indole alkaloids isolated from the barks of Voacanga africana Staph. - Hong-Mei Chen; Yu-Ting Yang; Hong-Xiang Li; Zhi-Xing Cao; Xiao-Mei Dan; Ling Mei; Da-Le Guo; Chuan-Xia Song; Yu Dai; Jia Hu; Yun Deng (Natural Product Research, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

CRMP1 Interacted with Spy1 During the Collapse of Growth Cones Induced by Sema3A and Acted on Regeneration After Sciatic Nerve Crush - Li Yao; Yong-hua Liu; Xiaohong Li; Yu-hong Ji; Xiao-jing Yang; Xian-ting Hang; Zong-mei Ding; Fang Liu; You-hua Wang; Ai-guo Shen (Molecular Neurobiology, 2016)

Effect of Boric Acid Supplementation on the Expression of BDNF in African Ostrich Chick Brain - Juan Tang; Xing-ting Zheng; Ke Xiao; Kun-lun Wang; Jing Wang; Yun-xiao Wang; Ke Wang; Wei Wang; Shun Lu; Ke-li Yang; Peng-Peng Sun; Haseeb Khaliq; et al. (Biological Trace Element Research, 2016)

Phytosterol content and the campesterol:sitosterol ratio influence cotton fiber development: role of phytosterols in cell elongation - Shasha Deng; Ting Wei; Kunling Tan; Mingyu Hu; Fang Li; Yunlan Zhai; Shue Ye; Yuehua Xiao; Lei Hou; Yan Pei; Ming Luo (Science China Life Sciences, 2016)

TNP-ATP is Beneficial for Treatment of Neonatal Hypoxia-Induced Hypomyelination and Cognitive Decline - Jie Xiao; Yilong Huang; Xia Li; Longjun Li; Ting Yang; Lixuan Huang; Ling Yang; Hong Jiang; Hongchun Li; Fan Li (Neuroscience Bulletin, 2016)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Long-term effects of oral tea polyphenols and Lactobacillus brevis M8 on biochemical parameters, digestive enzymes, and cytokines expression in broilers - Hua-li Li; Zong-jun Li; Zhong-shan Wei; Ting Liu; Xiao-zuo Zou; Yong Liao; Yu Luo (Journal of Zhejiang University-SCIENCE B, 2015)

Inhibition of myosin light chain kinase reduces NADPH oxidase-mediated oxidative injury in rat brain following cerebral ischemia/reperfusion - Hong-Feng Zhang; Ting-Bo Li; Bin Liu; Zheng Lou; Jie-Jie Zhang; Jing-Jie Peng; Xiao-Jie Zhang; Qi-Lin Ma; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Suppression of Chlorantraniliprole Sorption on Biochar in Soil–Biochar Systems - Ting-Ting Wang; Yi-Song Li; Alice C. Jiang; Meng-Xiao Lu; Xian-Jin Liu; Xiang-Yang Yu (Bulletin of Environmental Contamination and Toxicology, 2015)

Upregulation and Diverse Roles of TRPC3 and TRPC6 in Synaptic Reorganization of the Mossy Fiber Pathway in Temporal Lobe Epilepsy - Chang Zeng; Pinting Zhou; Ting Jiang; Chunyun Yuan; Yan Ma; Li Feng; Renkai Liu; Weiting Tang; Xiaoyan Long; Bo Xiao; Fafa Tian (Molecular Neurobiology, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Proteome analysis of pear reveals key genes associated with fruit development and quality - Jia Ming Li; Xiao San Huang; Lie Ting Li; Dan Man Zheng; Cheng Xue; Shao Ling Zhang; Jun Wu (Planta, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Immune protective effect of human alpha-1-antitrypsin gene during β cell transplantation in diabetic mice - Lu Yang; Yu-Ting Liao; Xiao-Fei Yang; Li-Wei Reng; Hui Qi; Fu-Rong Li (Immunologic Research, 2015)

Lower Serum Bilirubin and Uric Acid Concentrations in Patients with Parkinson’s Disease in China - Xiao-ling Qin; Qing-shan Zhang; Li Sun; Meng-wei Hao; Zhao-ting Hu (Cell Biochemistry and Biophysics, 2015)

Genome-Wide Identification, Expression, and Activity Analysis of Alkaline/Neutral Invertase Gene Family from Cassava (Manihot esculenta Crantz) - Yuan Yao; Meng-Ting Geng; Xiao-Hui Wu; Jiao Liu; Rui-Mei Li; Xin-Wen Hu; Jian-Chun Guo (Plant Molecular Biology Reporter, 2015)

Direct and indirect effects of nitrogen additions on fine root decomposition in a subtropical bamboo forest - Li-hua Tu; Yong Peng; Gang Chen; Hong-ling Hu; Yin-long Xiao; Ting-xing Hu; Li Liu; Yi Tang (Plant and Soil, 2015)

Simulation of long-term spring wheat yields, soil organic C, N and water dynamics using DSSAT-CSM in a semi-arid region of the Canadian prairies - Zhuo Ting Li; J. Y. Yang; W. N. Smith; C. F. Drury; R. L. Lemke; B. Grant; W. T. He; Xiao Gang Li (Nutrient Cycling in Agroecosystems, 2015)

Expression of neuropeptides and bone remodeling-related factors during periodontal tissue regeneration in denervated rats - Xijiao Yu; Linlin Lv; Jing Zhang; Ting Zhang; Changjie Xiao; Shu Li (Journal of Molecular Histology, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Secretomes are a potential source of molecular targets for cancer therapies and indicate that APOE is a candidate biomarker for lung adenocarcinoma metastasis - Zan Liu; Yuan Gao; Fengxia Hao; Xiaomin Lou; Xiuwei Zhang; Yang Li; Di Wu; Ting Xiao; Longhai Yang; Qingchang Li; Xueshan Qiu; Enhua Wang (Molecular Biology Reports, 2014)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

Microseismic monitoring of columnar jointed basalt fracture activity: a trial at the Baihetan Hydropower Station, China - Bing-Rui Chen; Qing-Peng Li; Xia-Ting Feng; Ya-Xun Xiao; Guang-Liang Feng; Lian-Xing Hu (Journal of Seismology, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Rapid development of tissue bank achieved by International Atomic Energy Agency (IAEA) Tissue Banking Programme in China - Yu-Min Zhang; Jian-Ru Wang; Nai-Li Zhang; Xiao-Ming Liu; Mo Zhou; Shao-Ying Ma; Ting Yang; Bao-Xing Li (Cell and Tissue Banking, 2014)

Sunitinib mesylate inhibits proliferation of human colonic stromal fibroblasts in vitro and in vivo - Zhan-huai Wang; Qiong Li; Shu-qin Ruan; Qian Xiao; Yue Liu; Ye-ting Hu; Li-feng Hu; Hai-yan Chen; Shu Zheng; Su-zhan Zhang; Ke-feng Ding (Journal of Zhejiang University-SCIENCE B, 2014)

Effect of pretreatment with hydrogen sulfide donor sodium hydrosulfide on heat tolerance in relation to antioxidant system in maize (Zea mays) seedlings - Zhong-Guang Li; Xiao-Yun Yi; Yu-Ting Li (Biologia, 2014)

A three‐component signalling system fine‐tunes expression kinetics of HPPK responsible for folate synthesis by positive feedback loop during stress response of X anthomonas campestris - Fang‐Fang Wang; Chao‐Ying Deng; Zhen Cai; Ting Wang; Li Wang; Xiao‐Zheng Wang; Xiao‐Ying Chen; Rong‐Xiang Fang; Wei Qian (Environmental Microbiology, 2014)
Summary During adaptation to environments, bacteria employ two‐component signal transduction systems, which contain histidine kinases and response regulators, to sense and respond to exogenous and cellular stimuli in an accurate spatio‐temporal manner. Although the protein phosphorylation process between histidine kinase and response regulator has been well documented, the molecular mechanism fine‐tuning phosphorylation levels of response regulators is comparatively less studied. Here we combined genetic and biochemical approaches to reveal that a hybrid histidine kinase, SreS , is involved in the SreK ‐ SreR phosphotransfer process to control salt stress response in the bacterium X anthomonas campestris . The N ‐terminal receiver domain of SreS acts as a phosphate sink by competing with the response regulator SreR to accept the phosphoryl group from the latter's cognate histidine kinase SreK . This regulatory process is critical for bacterial survival because the dephosphorylated SreR protein participates in activating one of the tandem promoters ( P 2) at the 5′ end of the sreK ‐ sreR ‐ sreS ‐ hppK operon, and then modulates a transcriptional surge of the stress‐responsive gene hppK , which is required for folic acid synthesis. Therefore, our study dissects the biochemical process of a positive feedback loop in which a ‘three‐component’ signalling system fine‐tunes expression kinetics of downstream genes.

Geochronology of magmatism and mineralization of the Daheishan giant porphyry molybdenum deposit, Jilin Province, Northeast China: constraints on ore genesis and implications for geodynamic setting - Ling-Li Zhou; Qing-Dong Zeng; Jian-Ming Liu; Henrik Friis; Zuo-Lun Zhang; Xiao-Xia Duan; Ting-Guang Lan (International Geology Review, 2014)

An approach based on antioxidant fingerprint–efficacy relationship and TLC bioautography assay to quality evaluation of Rubia cordifolia from various sources - Xu-Jie Zhang; Li-Juan Liu; Ting-Ting Song; Yan-Qiu Wang; Xiao-hong Yang (Journal of Natural Medicines, 2014)

An Experimental Study on the Pre-Peak Unloading Damage Evolution of Marble - Shi-Li Qiu; Xia-Ting Feng; Jian-Qing Xiao; Chuan-Qing Zhang (Rock Mechanics and Rock Engineering, 2014)

Meta-analysis of the association of glutathione S-transferase T1 null/presence gene polymorphism with the risk of gastric carcinoma - Yuan-Biao Meng; Xiao-Yong Cai; Wen-Qi Lu; Li-Hua Yang; Ting-Qing Gan; Gregor P. C. Drummen (Molecular Biology Reports, 2014)

Dissipation of available benzo[a]pyrene in aging soil co-contaminated with cadmium and pyrene - Kai Wang; Xin-xin Chen; Zhi-qiang Zhu; Hua-gang Huang; Ting-qiang Li; Xiao-e Yang (Environmental Science and Pollution Research, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Microbial Diversity and Succession in the Chinese Luzhou-Flavor Liquor Fermenting Cover Lees as Evaluated by SSU rRNA Profiles - Ke Li; Qing Zhang; Xiao-Ting Zhong; Bi-Hong Jia; Chun-Hong Yuan; Sen Liu; Zhen-Ming Che; Wen-Liang Xiang (Indian Journal of Microbiology, 2013)

The complete S RNA and M RNA nucleotide sequences of a hippeastrum chlorotic ringspot virus (HCRV) isolate from Hymenocallis littoralis (Jacq.) Salisb in China - Ye Xu; Shi-gao Lou; Xiao-lin Li; Yuan-xian Zheng; Wen-cheng Wang; Ya-ting Liu (Archives of Virology, 2013)

Genetic structure of rice black-streaked dwarf virus populations in China - Xiao Yin; Fang-Qiang Zheng; Wei Tang; Qin-Qin Zhu; Xiang-Dong Li; Guang-Min Zhang; Huan-Ting Liu; Bao-Shen Liu (Archives of Virology, 2013)

A New Thiophenyl Pyrazoline Fluorescent Probe for Cu2+ in Aqueous Solution and Imaging in Live Cell - Meng-Meng Li; Wen-Bo Zhao; Ting-Ting Zhang; Wei-Liu Fan; Yu Xu; Yu Xiao; Jun-Ying Miao; Bao-Xiang Zhao (Journal of Fluorescence, 2013)

Salegentibacter echinorum sp. nov., isolated from the sea urchin Hemicentrotus pulcherrimus - Hai-Feng Xia; Xiao-Li Li; Qian-Qian Liu; Ting-Ting Miao; Zong-Jun Du; Guan-Jun Chen (Antonie van Leeuwenhoek, 2013)

Up-regulation of Slc39A2(Zip2) mRNA in peripheral blood mononuclear cells from patients with pulmonary tuberculosis - Yan-ting Tao; Qing Huang; Ya-li Jiang; Xiao-lei Wang; Ping Sun; Yuanyuan Tian; Hai-liang Wu; Min Zhang; Si-bo Meng; Yu-shu Wang; Qing Sun; Lian-ying Zhang (Molecular Biology Reports, 2013)

Simultaneous removal of cadmium and sulfamethoxazole from aqueous solution by rice straw biochar - Xuan Han; Cheng-feng Liang; Ting-qiang Li; Kai Wang; Hua-gang Huang; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

The Very Large G Protein Coupled Receptor (Vlgr1) in Hair Cells - Jin-Peng Sun; Rong Li; Hong-Ze Ren; An-Ting Xu; Xiao Yu; Zhi-Gang Xu (Journal of Molecular Neuroscience, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Two new oleanane-type saponins from the husks of Xanthoceras sorbifolia Bunge - Ying-Ying Li; Zheng Xiang; Hao Cui; Hang Xiao; Ting-Guo Kang; De-Qiang Dou; Hai-Xue Kuang (Natural Product Research, 2013)

Improved cadmium uptake and accumulation in the hyperaccumulator Sedum alfredii: the impact of citric acid and tartaric acid - Ling-li Lu; Sheng-ke Tian; Xiao-e Yang; Hong-yun Peng; Ting-qiang Li (Journal of Zhejiang University-SCIENCE B, 2013)

Functional expression of ERG1 potassium channels in rat alveolar macrophages - Haiying Dong; Zhenyu Ji; Manling Liu; Yanxia Wang; Xiao Bai; Ting Wang; Zidong Liu; Yousheng Wu; Bo Zhang; Ying Luo; Zhichao Li; Mingqing Dong (Journal of Molecular Histology, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Exposure of silver carp (Hypophthalmichthys molitrix) to environmentally relevant levels of cadmium: hematology, muscle physiology, and implications for stock enhancement in the Xiangjiang River (Hunan, China) - Ting Zhang; Yu Zhang; DeLiang Li; TiaoYi Xiao; Jie Li (Science China Life Sciences, 2013)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

RETRACTED ARTICLE: A 2-D DIGE analysis of simulated acid rain-responsive proteins in Pinus massoniana needles - Ting-Wu Liu; Wen-Jun Hu; Xiao-Qin Wang; Li Niu; Bin Fu; Fei-Hua Wu; Zhen-Ming Pei; Hai-Lei Zheng (Trees, 2012)

Characterization of malleability and immunological properties of human adenovirus type 3 hexon hypervariable region 1 - Tianhua Zhong; Xiao Li; Zhichao Zhou; Ting Li; Xingui Tian; Rong Zhou (Archives of Virology, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Cadmium accumulation in different pakchoi cultivars and screening for pollution-safe cultivars - Ying Chen; Ting-qiang Li; Xuan Han; Zhe-li Ding; Xiao-e Yang; Ye-fei Jin (Journal of Zhejiang University-SCIENCE B, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Impact of simulated microgravity on microvascular endothelial cell apoptosis - Chun-Yan Kang; Lin Zou; Ming Yuan; Yang Wang; Tian-Zhi Li; Ye Zhang; Jun-Feng Wang; Yan Li; Xiao-Wei Deng; Chang-Ting Liu (European Journal of Applied Physiology, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Exogenous hydrogen peroxide can enhance tolerance of wheat seedlings to salt stress - Jin-Ting Li; Zong-Bo Qiu; Xiao-Wei Zhang; Lin-Song Wang (Acta Physiologiae Plantarum, 2011)

Enhanced biodesulfurization by magnetic immobilized Rhodococcus erythropolis LSSE8-1-vgb assembled with nano-γ-Al2O3 - Ting Zhang; Wang-Liang Li; Xiao-Xin Chen; Huang Tang; Qiang Li; Jian-Min Xing; Hui-Zhou Liu (World Journal of Microbiology and Biotechnology, 2011)

Novel 1-alkyl-tryptophan derivatives downregulate IDO1 and IDO2 mRNA expression induced by interferon-gamma in dendritic cells - Ting Sun; Xiang-Hua Chen; Zheng-De Tang; Jiong Cai; Xiao-Yan Wang; Shih-Chen Wang; Zhao-Long Li (Molecular and Cellular Biochemistry, 2010)

Isolation and characterization of polymorphic microsatellite loci in Aquilaria sinensis (Lour.) Gilg - Yan-Ting Zhang; Zheng-Feng Wang; Hong-Lin Cao; Xiao-Yi Li; Lin-Fang Wu; Shu-Bin Zhuo; Xiao-Feng Huang (Conservation Genetics Resources, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Effects of sazetidine-A, a selective α4β2 nicotinic acetylcholine receptor desensitizing agent on alcohol and nicotine self-administration in selectively bred alcohol-preferring (P) rats - Amir H. Rezvani; Susan Slade; Cori Wells; Ann Petro; Lawrence Lumeng; Ting-Kai Li; Yingxian Xiao; Milton L. Brown; Mikell A. Paige; Brian E. McDowell; Jed E. Rose; Kenneth J. Kellar; et al. (Psychopharmacology, 2010)

Electroporation is a feasible method to introduce circularized or linearized DNA into B. subtilis chromosome - Ming-Ming Yang; Wei-Wei Zhang; Xiao-Ting Bai; Heng-Xin Li; Pei-Lin Cen (Molecular Biology Reports, 2010)

Dynamics of soil organic carbon and nitrogen associated with physically separated fractions in a grassland-cultivation sequence in the Qinghai-Tibetan plateau - Xiao Ming Shi; Xiao Gang Li; Rui Jun Long; Bhupinder Pal Singh; Zhuo Ting Li; Feng Min Li (Biology and Fertility of Soils, 2010)

Dynamics of soil properties and organic carbon pool in topsoil of zokor-made mounds at an alpine site of the Qinghai–Tibetan Plateau - Xiao Gang Li; Mei Lan Zhang; Zhuo Ting Li; Xiao Ming Shi; Qifu Ma; Rui Jun Long (Biology and Fertility of Soils, 2009)

Activation of Group III Metabotropic Glutamate Receptor Reduces Intracellular Calcium in β-Amyloid Peptide [31–35]-Treated Cortical Neurons - Li Zhao; Shen Ting Zhao; Zhong Ming Qian; Ce Zhang; Xiao Mei Wu; Fang Du; Ya Ke (Neurotoxicity Research, 2009)

Singlet oxygen formation and chlorophyll a triplet excited state deactivation in the cytochrome b 6 f complex from Bryopsis corticulans - Fei Ma; Xiao-Bo Chen; Min Sang; Peng Wang; Jian-Ping Zhang; Liang-Bi Li; Ting-Yun Kuang (Photosynthesis Research, 2009)

Electroacupuncture Induced Spinal Plasticity is Linked to Multiple Gene Expressions in Dorsal Root Deafferented Rats - Xu-Yang Wang; Xiao-Li Li; Sun-Quan Hong; Yan-Bin Xi-Yang; Ting-Hua Wang (Journal of Molecular Neuroscience, 2009)

Characterization of tomato zonate spot virus, a new tospovirus in China - Jia-Hong Dong; Xiao-Fei Cheng; Yue-Yan Yin; Qi Fang; Ming Ding; Ting-Ting Li; Li-Zhen Zhang; Xiao-Xia Su; Jenifer Huang McBeath; Zhong-Kai Zhang (Archives of Virology, 2008)

Microbial activity and community diversity in a variable charge soil as affected by cadmium exposure levels and time - Jia-li Shentu; Zhen-li He; Xiao-e Yang; Ting-qiang Li (Journal of Zhejiang University-SCIENCE B, 2008)

Removal of hexavalent chromium by fungal biomass of Mucor racemosus: influencing factors and removal mechanism - Ting Liu; Huidong Li; Zhao Li; Xiao Xiao; Lingli Chen; Le Deng (World Journal of Microbiology and Biotechnology, 2007)

Repair of glutamate-induced excitotoxic neuronal damage mediated by intracerebroventricular transplantation of neural stem cells in adult mice - Juan Ma; Li-Jian Yu; Run-Di Ma; Yong-Ping Zhang; Juan-Zhi Fang; Xiao-Yu Zhang; Ting-Xi Yu (Neuroscience Bulletin, 2007)

Hydrogen peroxide-induced chlorophyll a bleaching in the cytochrome b 6 f complex: a simple and effective assay for stability of the complex in detergent solutions - Xiao-Bo Chen; Xiao-Hui Zhao; Yi Zhu; Yan-Dao Gong; Liang-Bi Li; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2007)

Preparation and Fluoroimmunoassay Application of New Red-Region Fluorescent Silica Nanoparticles - Xiao-Lan Chen; Jian-Li Zou; Ting-Ting Zhao; Zhong-Bao Li (Journal of Fluorescence, 2007)

Zinc adsorption and desorption characteristics in root cell wall involving zinc hyperaccumulation in Sedum alfredii Hance - Ting-qiang Li; Xiao-e Yang; Fan-hua Meng; Ling-li Lu (Journal of Zhejiang University-SCIENCE B, 2007)

Functional analysis of helicase and three tandem HRDC domains of RecQ in Deinococcus radiodurans - Li-fen Huang; Xiao-ting Hua; Hui-ming LU; Guan-jun Gao; Bing Tian; Bing-hui Shen; Yue-jin Hua (Journal of Zhejiang University-SCIENCE B, 2006)

Study on energy transfer between carotenoid and chlorophyll a in cytochrome b 6 f complex from Bryopsis corticulans - Bin-Xing Li; Ping Zuo; Xiao-Bo Chen; Liang-Bi Li; Jian-Ping Zhang; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2006)